Pneumatic tires

JP7632535B2Active Publication Date: 2025-02-19SUMITOMO RUBBER INDUSTRIES LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023130211
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-19
Estimated Expiration
2039-05-29

Smart Images

  • Figure 0007632535000001
    Figure 0007632535000001
  • Figure 0007632535000002
    Figure 0007632535000002
  • Figure 0007632535000003
    Figure 0007632535000003
Patent Text Reader

Abstract

To provide a pneumatic tire having excellent tire performance such as low fuel consumption, wear resistance, wet grip performance, performance on snow and ice, puncture resistance, flex cracking growth resistance and the like.SOLUTION: A heavy load tire comprising a rubber composition that has a tread prepared with a rubber composition containing a natural rubber derived from Russian dandelion having a weight-average molecular weight Mw measured by FFF-MALS of 5,000,000 or larger and a radius of gyration Rz of a polymer of 130 nm or larger, and carbon black, in which a content of the Russian dandelion-derived natural rubber in 100 mass% of the rubber component is 1 mass% or larger, and a content of the carbon black relative to 100 pts.mass of the rubber component is 30 pts.mass or larger.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pneumatic tire. [Background technology]

[0002] In recent years, due to the social demand for energy and resource conservation, there is a high demand for improved durability of tires, and natural rubber is widely used as a rubber material with excellent fracture resistance, abrasion resistance, and crack growth resistance. Natural rubber is generally produced from Hevea (Hevea brasiliensis: rubber tree) cultivated in subtropical regions, such as Indonesia, Thailand, and Malaysia.

[0003] Recently, the global production of tires has been on the rise, and the use of natural rubber has been increasing accordingly, but rubber trees are currently only cultivated in subtropical regions, and it cannot be denied that supply and prices are unstable. In addition, there is an increasing demand for tire performance, such as low fuel consumption, wear resistance, and fracture resistance, and improvements in these properties are being demanded of the commonly used natural rubber.

[0004] For example, various studies have been conducted, such as epoxy modification of natural rubber, introduction of ultra-high molecular weight components by adding a crosslinking agent, and synthesis of synthetic polyisoprene with an increased cis content, but further performance improvements are desired (see Patent Document 1). In addition, the production costs are high, and the reality is that there is little merit in terms of price. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-205960 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has an object to solve the above problems and to provide a pneumatic tire that has excellent tire performance such as fuel economy, wear resistance, wet grip performance, performance on snow and ice, fracture resistance, and flex crack growth resistance. [Means for solving the problem]

[0007] The present invention relates to a heavy duty tire having a tread made using a rubber composition containing Russian dandelion-derived natural rubber and carbon black, the natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a polymer radius of gyration Rz of 130 nm or more, wherein the rubber composition has a content of Russian dandelion-derived natural rubber of 1 mass% or more in 100 mass% of a rubber component, and a content of carbon black of 30 parts by mass or more per 100 parts by mass of the rubber component.

[0008] The present invention relates to a heavy-duty tire having a tread made using a rubber composition containing Russian dandelion-derived natural rubber having a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of polymers in the weight-average molecular weight range of Mw of 5 million to 50 million of 130 nm or more, and carbon black, wherein the rubber composition has a content of Russian dandelion-derived natural rubber of 1 mass% or more in 100 mass% of a rubber component, and a content of carbon black of 30 parts by mass or more per 100 parts by mass of the rubber component.

[0009] The present invention relates to a heavy-duty tire having a tread made using a rubber composition containing Russian dandelion-derived natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line having a slope of 0.25 or more in a region of a weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm of the weight average molecular weight Mw (logMw) versus the common logarithm of the radius of gyration Rz of the polymer (logRz), and carbon black, wherein the rubber composition has a content of Russian dandelion-derived natural rubber of 1 mass% or more in 100 mass% of a rubber component and a content of carbon black of 30 parts by mass or more per 100 parts by mass of the rubber component.

[0010] The present invention relates to a natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The present invention relates to an all-season tire having a tread made using a rubber composition containing 100 parts by mass of a rubber component having a content of the Russian dandelion-derived natural rubber of 1% by mass or more and a content of the silica per 100 parts by mass of the rubber component of 10 parts by mass or more.

[0011] The present invention relates to a natural rubber derived from a Russian dandelion, which has a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight-average molecular weight range of Mw 5 million to 50 million of 130 nm or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The present invention relates to an all-season tire having a tread made using a rubber composition containing 100 parts by mass of a rubber component having a content of the Russian dandelion-derived natural rubber of 1% by mass or more and a content of the silica per 100 parts by mass of the rubber component of 10 parts by mass or more.

[0012] The present invention relates to a natural rubber derived from a Russian dandelion, which has a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS, and in which the slope of a linear regression line in the weight-average molecular weight region of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight-average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer is 0.25 or more; carbon black; and 2 The present invention relates to an all-season tire having a tread made using a rubber composition containing 100 parts by mass of a rubber component having a content of the Russian dandelion-derived natural rubber of 1% by mass or more and a content of the silica per 100 parts by mass of the rubber component of 10 parts by mass or more.

[0013] The present invention relates to a natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, a styrene-butadiene rubber having a styrene content of 10 mass% or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The present invention relates to a summer tire having a tread made of a rubber composition containing 0.1 to 10.0 mass% of the Russian dandelion-derived natural rubber in 100 mass% of a rubber component, and 10 parts by mass or more of the silica per 100 parts by mass of the rubber component.

[0014] The present invention relates to a natural rubber derived from a Russian dandelion, the weight-average molecular weight Mw of which is 5 million or more as measured by FFF-MALS, and the average value of the radius of gyration Rz of the polymer in the weight-average molecular weight range of Mw 5 million to 50 million is 130 nm or more, a styrene-butadiene rubber with a styrene content of 10 mass% or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica, The rubber composition has a content of the Russian dandelion-derived natural rubber in 100% by mass of a rubber component of 0.1 to 10.0% by mass, and the content of the silica in 100 parts by mass of the rubber component is 10 parts by mass or more.

[0015] The present invention relates to a natural rubber derived from a Russian dandelion, which has a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and in which the slope of a linear regression line in a weight-average molecular weight region of Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight-average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer is 0.25 or more, a styrene-butadiene rubber having a styrene content of 10% by mass or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2The present invention relates to a summer tire having a tread made of a rubber composition containing 0.1 to 10.0 mass% of the Russian dandelion-derived natural rubber in 100 mass% of a rubber component, and 10 parts by mass or more of the silica per 100 parts by mass of the rubber component.

[0016] The present invention relates to a natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, a butadiene rubber having a cis-1,4-bond content of 94.0 mass % or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The present invention relates to a studless tire having a tread made using a rubber composition containing 100 parts by mass of a rubber component, the content of the Russian dandelion-derived natural rubber being 1% by mass or more, the content of the butadiene rubber being 20 to 64% by mass, and the content of the silica being 5 parts by mass or more per 100 parts by mass of the rubber component.

[0017] The present invention relates to a natural rubber derived from Russian dandelion, which has a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight-average molecular weight range of Mw 5 million to 50 million of 130 nm or more, a butadiene rubber having a cis-1,4-bond content of 94.0 mass % or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The present invention relates to a studless tire having a tread made using a rubber composition containing 100 parts by mass of a rubber component, the content of the Russian dandelion-derived natural rubber being 1% by mass or more, the content of the butadiene rubber being 20 to 64% by mass, and the content of the silica being 5 parts by mass or more per 100 parts by mass of the rubber component.

[0018] The present invention relates to a natural rubber derived from Russian dandelion, which has a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line in a weight-average molecular weight region of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight-average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer, with a slope of 0.25 or more; butadiene rubber having a cis-1,4-bond content of 94.0 mass% or more; carbon black; and a nitrogen adsorption specific surface area of ​​40 m. 2 The present invention relates to a studless tire having a tread made using a rubber composition containing 100 parts by mass of a rubber component, the content of the Russian dandelion-derived natural rubber being 1% by mass or more, the content of the butadiene rubber being 20 to 64% by mass, and the content of the silica being 5 parts by mass or more per 100 parts by mass of the rubber component.

[0019] The present invention relates to a tire having a base tread made using a rubber composition containing Russian dandelion-derived natural rubber having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more, as measured by FFF-MALS, carbon black, and silica, wherein the rubber composition has a content of Russian dandelion-derived natural rubber of 1 mass% or more in 100 mass% of a rubber component, and a content of silica of 10 parts by mass or more per 100 parts by mass of the rubber component.

[0020] The present invention relates to a tire having a base tread made using a rubber composition containing Russian dandelion-derived natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight average molecular weight range of Mw of 5 million to 50 million of 130 nm or more, carbon black, and silica, wherein the rubber composition has a content of Russian dandelion-derived natural rubber of 1 mass% or more in 100 mass% of a rubber component, and a content of silica of 10 parts by mass or more per 100 parts by mass of the rubber component.

[0021] The present invention relates to a tire having a base tread made using a rubber composition containing Russian dandelion-derived natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line in a weight average molecular weight region of 5 million to 50 million with a slope of 0.25 or more in a plot of the common logarithm of the weight average molecular weight Mw (logMw) versus the common logarithm of the radius of gyration Rz of the polymer (logRz), carbon black, and silica, wherein the rubber composition has a content of Russian dandelion-derived natural rubber of 1 mass% or more in 100 mass% of a rubber component, and a content of silica of 10 parts by mass or more per 100 parts by mass of the rubber component.

[0022] The present invention relates to a tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a polymer radius of gyration Rz of 130 nm or more, and carbon black and / or silica.

[0023] The present invention relates to a tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight average molecular weight range of Mw of 5 million to 50 million of 130 nm or more, and carbon black and / or silica.

[0024] The present invention relates to a tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line having a slope of 0.25 or more in the weight average molecular weight region of 5 million to 50 million in a plot of the common logarithm of the weight average molecular weight Mw (logMw) versus the common logarithm of the radius of gyration Rz of the polymer (logRz), and carbon black and / or silica.

[0025] The present invention relates to a tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, the natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a polymer radius of gyration Rz of 130 nm or more, and carbon black and / or silica.

[0026] The present invention relates to a tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight average molecular weight range of Mw of 5 million to 50 million of 130 nm or more, and carbon black and / or silica.

[0027] The present invention relates to a tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line having a slope of 0.25 or more in a region of a weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer, and carbon black and / or silica. Effect of the Invention

[0028] According to the present invention, a heavy-duty tire or the like has a tread made using a rubber composition containing Russian dandelion-derived natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a polymer radius of gyration Rz of 130 nm or more, and carbon black, wherein the rubber composition contains 1 mass% or more of the Russian dandelion-derived natural rubber in 100 mass% of the rubber component, and the carbon black is contained in an amount of 1 part by mass or more per 100 parts by mass of the rubber component, and therefore can impart tire performance such as excellent fuel efficiency, abrasion resistance, wet grip performance, performance on snow and ice, fracture resistance, and flex crack growth resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] [Heavy-duty tires] (Rubber component) The present invention relates to heavy-duty tires (tires for trucks, buses, etc.) as described below in (1) to (3). A specific Russian dandelion-derived natural rubber and carbon black are used in combination in a specified blend, which significantly (synergistically) improves the overall performance of fuel economy, wear resistance, and wet grip performance. In addition, the Russian dandelion is an annual plant that grows in temperate regions, and compared to the subtropics, the arable land is wider in Asia, North America, and Europe, making it possible to diversify the supply risk of natural rubber.

[0030] (1) A first heavy-duty tire having a tread made using a rubber composition containing, in a predetermined ratio, natural rubber derived from Russian dandelion, the natural rubber having a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and a polymer radius of gyration Rz of 130 nm or more, and carbon black.

[0031] (2) A second heavy-duty tire having a tread made using a rubber composition containing, in a predetermined ratio, natural rubber derived from Russian dandelion, having a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average radius of gyration Rz of polymers in the weight-average molecular weight range of Mw 5 million to 50 million of 130 nm or more, and carbon black.

[0032] (3) A third heavy-duty tire having a tread made using a rubber composition containing, in a predetermined blend, natural rubber derived from Russian dandelion, which has a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line having a slope of 0.25 or more in the weight-average molecular weight region of 5 million to 50 million in a plot of the common logarithm of the weight-average molecular weight Mw (logMw) versus the common logarithm of the radius of gyration Rz of the polymer (logRz).

[0033] The reason (mechanism) why the overall performance of fuel economy, wear resistance, and wet grip performance is significantly (synergistically) improved is not necessarily clear, but is presumed to be as follows. The specific Russian dandelion-derived natural rubber of the present application has a higher Mw and contains a large amount of high molecular weight components compared to Hevea-derived natural rubber, which increases the breaking strength of the rubber. Also, the Russian dandelion-derived natural rubber has a lower degree of branching and contains a larger amount of linear polymers compared to Hevea-derived natural rubber, which increases the Rz of the polymer. Therefore, the high Rz of the polymer increases entanglement between polymers, and the increased probability of contact between the polymer and the filler increases interaction with the filler, which improves reinforcing properties, breaking properties, abrasion resistance, wet grip performance, etc.

[0034] Furthermore, the specific Russian dandelion-derived natural rubber of the present application has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, resulting in fewer free molecular ends and therefore fewer components that cause hysteresis loss, resulting in excellent low heat generation.

[0035] It is presumed that the combined use of such natural rubber derived from Russian dandelion and carbon black will result in a significant (synergistic) improvement in the overall performance of fuel economy, abrasion resistance and wet grip performance.

[0036] The Russian dandelion-derived natural rubber in the first to third heavy-duty tires has a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS (field flow fractionation apparatus (FFF) and multi-angle light scattering detector (MALS)). By making it equal to or higher than the lower limit, the mechanical strength of the rubber increases, and there is a tendency for abrasion resistance, wet grip performance, performance on snow and ice, fracture resistance, flex crack growth resistance, and the like to be improved. It is preferably 5,050,000 or more, and more preferably 5,070,000 or more. There is no particular upper limit, and a larger Mw is more preferable, but from the viewpoint of deterioration of processability due to high viscosity, it is preferably 20 million or less, and more preferably 10 million or less.

[0037] The Russian dandelion-derived natural rubber in the first to third heavy-duty tires has a weight average molecular weight Mw / number average molecular weight Mn (Mw / Mn: molecular weight distribution) measured by FFF-MALS (field flow fractionation apparatus (FFF) and multi-angle light scattering detector (MALS)) of preferably 2.40 or less, more preferably 2.20 or less, even more preferably 2.00 or less, and particularly preferably 1.90 or less. By setting it to the upper limit or less, the mechanical strength of the rubber increases, and there is a tendency that abrasion resistance, wet grip performance, performance on snow and ice, fracture resistance, flex crack growth resistance, etc. are improved. There is no particular restriction on the lower limit, and a smaller Mw / Mn is preferable, but from the viewpoint of deterioration of processability due to narrow molecular weight distribution, it is preferably 1.00 or more, and more preferably 1.50 or more.

[0038] In addition, from the standpoint of tire performance such as fuel economy, abrasion resistance, wet grip performance, performance on snow and ice, fracture resistance, and flex crack growth resistance, it is preferable that the Russian dandelion-derived natural rubber for the first to third heavy load uses be a rubber having a monodisperse molecular weight distribution, as indicated by the relationship between Molar Mass (g / mol) and Mass Distribution, for example.

[0039] The Russian dandelion-derived natural rubber in the first heavy-duty tire has a polymer radius of gyration Rz (Rz of all the polymers constituting the Russian dandelion-derived natural rubber) of 130 nm or more. By making it equal to or greater than the lower limit, the mechanical strength of the rubber increases, and there is a tendency for abrasion resistance, wet grip performance, performance on snow and ice, fracture resistance, flex crack growth resistance, and the like to be improved. There is also a tendency for low heat build-up properties to be improved. It is preferably 133 nm or more, more preferably 135 nm or more. There is no particular upper limit, and a larger Rz is more preferable, but from the viewpoint of deterioration of processability due to a small amount of branched polymer, it is preferably 300 nm or less, more preferably 250 nm or less.

[0040] The Russian dandelion-derived natural rubber in the second heavy-duty tire has an average radius of gyration Rz of polymers in a weight-average molecular weight range of Mw 5 million to 50 million of 130 nm or more. Here, the "average radius of gyration Rz of polymers in a weight-average molecular weight range of Mw 5 million to 50 million" refers to the average value of each Rz value measured at each Mw in the range of 5 million to 50 million in Mw and Rz obtained using FFF-MALS. For example, when the Mw values ​​and Rz values ​​in the range of Mw 5 million to 50 million are (Mw1, Rz1), (Mw2, Rz2), ..., (Mw n ,Rz n ), then (Rz1+Rz2+···+Rz n The number of data n can be appropriately selected from within a range of Mw 5 million to 50 million, and for example, about 300 to 500 pieces of data may be obtained.

[0041] By making the average value equal to or greater than the lower limit, the mechanical strength of the rubber increases, and there is a tendency for the wear resistance, wet grip performance, snow and ice performance, fracture resistance, and flex crack growth resistance to be improved. There is also a tendency for the low heat buildup property to be improved. It is preferably 150 nm or more, more preferably 160 nm or more, even more preferably 170 nm or more, and particularly preferably 180 nm or more. There is no particular restriction on the upper limit, and the larger the average value, the more preferable it is, but from the viewpoint of deterioration of processability due to a small amount of branched polymer, it is preferably 250 nm or less, and more preferably 240 nm or less.

[0042] The Russian dandelion-derived natural rubber in the third heavy-duty tire has a gradient of a linear regression line in a region of weight-average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight-average molecular weight Mw versus the common logarithm (logRz) of the polymer radius of gyration Rz of the weight-average molecular weight Mw of 0.25 or more. Here, "the gradient of a linear regression line in a region of weight-average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight-average molecular weight Mw versus the common logarithm (logRz) of the polymer radius of gyration Rz of the weight-average molecular weight Mw" refers to the gradient of a linear regression line prepared in a region of Mw of 5 million to 50 million in a diagram plotting the common logarithm of each Rz at each Mw obtained using FFF-MALS.

[0043] The approximation of the linear regression line can be performed by using a commonly known statistical method, for example, a method of approximating a regression line (approximation line) using the least squares method. Specifically, in a plot of logMw versus logRz, the data points (logMw1, logRz1), (logMw2, logRz2), . . . , (logMw n ,logRz n ) is determined by, for example, the least squares method. The number of data n can be appropriately selected from within the range of Mw 5 million to 50 million, and for example, about 300 to 500 pieces of data may be obtained.

[0044] By making the slope equal to or greater than the lower limit, the mechanical strength of the rubber increases, and the abrasion resistance, wet grip performance, performance on snow and ice, fracture resistance, flex crack growth resistance, etc. tend to improve. There is also a tendency for low heat buildup to improve. It is preferably 0.26 or more, more preferably 0.28 or more, even more preferably 0.30 or more, and particularly preferably 0.32 or more. There is no particular limit to the upper limit, and a larger average value is more preferable, but from the viewpoint of deterioration of processability due to a small amount of branched polymer, it is preferably 0.60 or less, and more preferably 0.50 or less.

[0045] Here, the FFF-MALS used for measuring Mw and Rz is an apparatus equipped with a field flow fractionation (FFF) apparatus and a multi-angle light scattering (MALS) detector. The FFF apparatus is an apparatus that can fractionate molecular weights by passing a sample solution through a gap (channel) of, for example, 100 μm to 500 μm and applying a field when passing through the channel. The field application method includes centrifugal force, temperature difference, electric field, etc., but an asymmetric flow FFF apparatus is preferable. Specifically, a sample (rubber) is dissolved in a solvent, and the obtained rubber solution is subjected to an FFF apparatus equipped with a MALS detector and a differential refractometer (RI detector), and Mw and Rz can be measured by adopting a method of performing a Debye plot from the obtained values, etc.

[0046] The organic solvent used to dissolve the sample (natural rubber derived from Russian dandelion) is not particularly limited, and any solvent capable of dissolving the sample can be used. For example, tetrahydrofuran (THF), chloroform, toluene, cyclohexane, etc. can be used alone or in combination. Among them, THF is preferable because of its good solubility. The sample concentration (concentration of natural rubber derived from Russian dandelion) in the organic solvent is preferably adjusted to 0.001 to 1% by mass. For example, a completely dissolved solution can be prepared by adding the sample to the organic solvent, adjusting the concentration to the above range, and leaving it for 12 hours or more.

[0047] In this specification, the Mw, Mn, polymer Rz, average polymer Rz value and slope of the linear regression line of the Russian dandelion-derived natural rubber are measured in detail by the method described in the Examples below.

[0048] The specific natural rubber derived from Russian dandelion of the present application can be obtained, for example, by the extraction methods described in U.S. Patent Publications US2019 / 0048101A1 and US2019 / 0046895A1.

[0049] The first to third heavy duty tires each have a tread made of a rubber composition containing the natural rubber derived from the Russian dandelion and carbon black in a predetermined blend.

[0050] In the rubber composition, the content of the Russian dandelion-derived natural rubber is 1% by mass or more, preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 50% by mass or more, and particularly preferably 65% ​​by mass or more, based on 100% by mass of the rubber component. The upper limit is not particularly limited, but is preferably 90% by mass or less, more preferably 85% by mass or less. By keeping the content within the above range, the overall performance of fuel economy, abrasion resistance, and wet grip performance is significantly improved.

[0051] The rubber composition may contain other rubber components together with the Russian dandelion-derived natural rubber. Examples of the other rubber components include diene rubbers such as natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene rubber (SIR), styrene isoprene butadiene rubber (SIBR), ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), acrylonitrile butadiene rubber (NBR), and butyl rubber (IIR). The rubber components may be used alone or in combination of two or more. The rubber components may be either unmodified or modified rubber. Among them, BR is preferred from the viewpoint of overall performance of fuel economy, wear resistance, and wet grip performance.

[0052] The BR is not particularly limited, and for example, high-cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. can be used. These may be used alone or in combination of two or more. The BR may be unmodified or modified. Of these, high-cis BR with a cis content of 90% by mass or more is preferred because it improves abrasion resistance, etc.

[0053] The BR may also preferably be a modified BR (modified conjugated diene polymer) obtained by a production method that includes a modification step (A) of carrying out a modification reaction of introducing an alkoxysilane compound having two or more reactive groups, including an alkoxysilyl group, to the active terminal of polybutadiene having a cis-1,4-bond content of 94.0 mass% or more and having an active terminal, and a condensation step (B) of carrying out a condensation reaction of a residue of the alkoxysilane compound introduced to the active terminal in the presence of a condensation catalyst containing at least one element selected from the group consisting of elements included in groups 4, 12, 13, 14, and 15 of the periodic table, and that uses, as the polybutadiene, a polybutadiene polymerized in the presence of a catalyst composition containing, as a main component, a mixture of the following components (a) to (c): Component (a): a lanthanoid-containing compound containing at least one element selected from the group consisting of lanthanoids, or a reaction product obtained by reacting the lanthanoid-containing compound with a Lewis base. Component (b): Aluminoxane and a compound represented by the general formula (1); AlR 1 R 2 R 3 (wherein, in the general formula (1), R 1 and R 2 R are the same or different and represent a hydrocarbon group having 1 to 10 carbon atoms or a hydrogen atom. 3 is R 1 and R 2 and represents a hydrocarbon group having 1 to 10 carbon atoms. (c) Component: an iodine-containing compound that contains at least one iodine atom in its molecular structure.

[0054] That is, the modified BR (modified conjugated diene polymer) can be produced by carrying out a modification reaction in which an alkoxysilane compound is introduced into the active terminal of polybutadiene having a cis-1,4-bond content of 94.0% by mass or more, and then carrying out a condensation reaction of the alkoxysilane compound residue of the alkoxysilane compound introduced into the active terminal in the presence of a condensation catalyst containing at least one element selected from the elements contained in groups 4, 12, 13, 14, and 15 of the periodic table. An example of such a modified BR is the modified BR (modified conjugated diene polymer) described in JP 2015-232112 A.

[0055] The above-mentioned modification step (A) is a step of carrying out a modification reaction in which an alkoxysilane compound having two or more reactive groups, including an alkoxysilyl group, is introduced into the active terminal of polybutadiene having a cis-1,4-bond content of 94.0 mass% or more and having an active terminal.

[0056] The polybutadiene is a conjugated diene polymer having a cis-1,4-bond content of 94.0% by mass or more and an active terminal. The cis-1,4-bond content is preferably 94.6% by mass or more, more preferably 98.5% by mass or more, even more preferably 99.0% by mass or more, and particularly preferably 99.2% by mass or more. In this specification, the cis-1,4-bond content (cis content) is a value calculated from the signal intensity measured by NMR analysis.

[0057] Regarding the component (a), preferred examples of the lanthanoid-containing compound include neodymium phosphate and neodymium carboxylate, and neodymium versatate and neodymium 2-ethylhexanoate are most preferred.Specific examples of the Lewis base include acetylacetone, tetrahydrofuran, pyridine, N,N-dimethylformamide, thiophene, diphenyl ether, triethylamine, organic phosphorus compounds, monohydric or dihydric alcohols, etc.

[0058] Regarding the above component (b), specific examples of the alumoxane include methylalumoxane (hereinafter also referred to as "MAO"), ethylalumoxane, n-propylalumoxane, n-butylalumoxane, isobutylalumoxane, t-butylalumoxane, hexylalumoxane, isohexylalumoxane, etc. Among these, MAO is preferred.

[0059] Specific examples of the organoaluminum compound represented by the general formula (1) include trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-t-butylaluminum, tripentylaluminum, trihexylaluminum, tricyclohexylaluminum, trioctylaluminum, diethylaluminum hydride, di-n-propylaluminum hydride, di-n-butylaluminum hydride, diisobutylaluminum hydride, dihexylaluminum hydride, diisohexylaluminum hydride, dioctylaluminum hydride, diisooctylaluminum hydride, ethylaluminum dihydride, n-propylaluminum dihydride, isobutylaluminum dihydride, etc. Among these, diisobutylaluminum hydride, triethylaluminum, triisobutylaluminum, and diethylaluminum hydride are preferred, and diisobutylaluminum hydride is particularly preferred.

[0060] Regarding the component (c), preferred examples of the iodine-containing compound include iodine, trimethylsilyl iodide, triethylsilyl iodide, dimethylsilyl diiodide, methyl iodide, iodoform, and diiodomethane, and trimethylsilyl iodide is the most preferred.

[0061] The blending ratio of each of the above components (components (a) to (c)) may be appropriately set as necessary, and the ratios described in JP 2015-232112 A can be used.

[0062] The polybutadiene (conjugated diene polymer) used in producing the modified BR (modified conjugated diene polymer) preferably has a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) measured by gel permeation chromatography, i.e., a molecular weight distribution (Mw / Mn) of 3.5 or less, more preferably 3.0 or less, and even more preferably 2.5 or less. In this specification, the Mw and Mn of the polymer other than the Russian dandelion-derived natural rubber can be determined in terms of standard polystyrene based on measurements obtained by gel permeation chromatography (GPC) (GPC-8000 series, manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M, manufactured by Tosoh Corporation).

[0063] The Mooney viscosity (ML) of the polybutadiene (conjugated diene polymer) at 100°C 1+4, 100°C) is preferably 5 to 50, more preferably 10 to 40. The Mooney viscosity (ML 1+4 , 100℃) was measured in accordance with JIS K 6300 using an L rotor, with 1 minute of preheating, 4 minutes of rotor operation time, and a temperature of 100℃.

[0064] The content of 1,2-vinyl bonds (1,2-vinyl bond amount) of the polybutadiene (conjugated diene polymer) is preferably 0.5% by mass or less, more preferably 0.4% by mass or less, and even more preferably 0.3% by mass or less. The 1,2-vinyl bond amount is preferably 0.001% by mass or more, and more preferably 0.01% by mass or more. In this specification, the 1,2-vinyl bond amount is a value calculated from the signal intensity measured by NMR analysis.

[0065] The alkoxysilane compound (hereinafter also referred to as "modifier") used in the above modification step (A) includes a compound having two or more reactive groups including an alkoxysilyl group. The reactive group other than the alkoxysilyl group is not particularly limited in type, but is preferably at least one functional group selected from the group consisting of (f) an epoxy group, (g) an isocyanate group, (h) a carbonyl group, and (i) a cyano group.

[0066] As the alkoxysilane compound (modifier), 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-cyanopropyltrimethoxysilane are particularly preferred, and 3-glycidoxypropyltrimethoxysilane is the most preferred. Also, partial condensates of the above-mentioned alkoxysilane compounds can be used.

[0067] In the modification reaction of the modification step (A), the amount of the alkoxysilane compound used is preferably 0.01 to 200 mol, and more preferably 0.1 to 150 mol, per 1 mol of the component (a).

[0068] In the modification step (A), in addition to the above-mentioned modifying agent, it is preferable to further add a substance that undergoes a condensation reaction with the alkoxysilane compound residue, which is the modifying agent introduced to the active terminal, in the condensation step (B) and is consumed. Specifically, it is preferable to add a functional group introducing agent.

[0069] The functional group introduction agent is not particularly limited as long as it does not substantially react directly with the active terminal and remains as an unreacted substance in the reaction system, but for example, it is preferable that it is an alkoxysilane compound different from the alkoxysilane compound used as the modifying agent, that is, an alkoxysilane compound containing at least one functional group selected from the group consisting of (j); amino group, (k); imino group, and (l); mercapto group. The alkoxysilane compound used as the functional group introduction agent may be a partial condensate, or may be a mixture of the alkoxysilane compound used as the functional group introduction agent that is not a partial condensate and the partial condensate.

[0070] Suitable examples of the functional group introducing agent include 3-diethylaminopropyl(triethoxy)silane, 3-dimethylaminopropyl(triethoxy)silane, 3-aminopropyltriethoxysilane, 3-(1-hexamethyleneimino)propyl(triethoxy)silane, N-(1-methylpropylidene)-3-(triethoxysilyl)-1-propanamine, N-(1,3-dimethylbutylidene)-3-(triethoxysilyl)-1-propanamine, 3-(1-hexamethylene Particularly preferred are (1-hexamethyleneimino)propyl(triethoxy)silane, (1-hexamethyleneimino)methyl(trimethoxy)silane, 1-[3-(triethoxysilyl)propyl]-4,5-dihydroimidazole, 1-[3-(trimethoxysilyl)propyl]-4,5-dihydroimidazole, N-(3-triethoxysilylpropyl)-4,5-dihydroimidazole, and 3-mercaptopropyltriethoxysilane, and most preferred is 3-aminopropyltriethoxysilane.

[0071] When an alkoxysilane compound is used as the functional group introducing agent, the amount used is preferably 0.01 to 200 mol, and more preferably 0.1 to 150 mol, per 1 mol of the component (a).

[0072] The condensation step (B) is a step of subjecting the residue of the alkoxysilane compound introduced into the active terminal to a condensation reaction in the presence of a condensation catalyst containing at least one element selected from the group consisting of elements in groups 4, 12, 13, 14 and 15 of the periodic table.

[0073] The condensation catalyst is not particularly limited as long as it contains at least one element selected from the group consisting of elements included in Groups 4, 12, 13, 14, and 15 of the periodic table. For example, it is preferable that the condensation catalyst contains at least one element selected from the group consisting of titanium (Ti) (Group 4), tin (Sn) (Group 14), zirconium (Zr) (Group 4), bismuth (Bi) (Group 15), and aluminum (Al) (Group 13).

[0074] A suitable example of the condensation catalyst is a condensation catalyst containing titanium (Ti). Among the condensation catalysts containing titanium (Ti), titanium (Ti) alkoxide, carboxylate, or acetylacetonate complex salt is more preferable. Particularly preferable is tetraisopropyl titanate (tetraisopropyl titanate).

[0075] The amount of the condensation catalyst used is preferably 0.1 to 10 moles, particularly preferably 0.3 to 5 moles, based on 1 mole of the total amount of alkoxysilyl groups present in the reaction system, in terms of the number of moles of the various compounds that can be used as the condensation catalyst.

[0076] After the condensation reaction is carried out as described above, a conventionally known post-treatment can be carried out to obtain the desired modified BR (modified conjugated diene polymer).

[0077] The Mooney viscosity (ML 1+4 (125° C.)) is preferably from 10 to 150, more preferably from 20 to 100. The Mooney viscosity (ML 1+4, 125°C) was measured in accordance with JIS K 6300 using an L rotor, with 1 minute of preheating, 4 minutes of rotor operation, and a temperature of 125°C.

[0078] The molecular weight distribution (Mw / Mn) of the modified BR (modified conjugated diene polymer) is preferably 3.5 or less, more preferably 3.0 or less, and even more preferably 2.5 or less.

[0079] The cold flow value (mg / min) of the modified BR (modified conjugated diene polymer) is preferably 1.0 or less, more preferably 0.8 or less. In this specification, the cold flow value (mg / min) is measured at a pressure of 3.5 lb / in. 2 This value was measured by extruding the polymer through a 1 / 4 inch orifice at a temperature of 50°C. To reach a steady state, the extrusion rate was measured after leaving it for 10 minutes, and the measured value was expressed in milligrams per minute (mg / min).

[0080] The evaluation value of the temporal stability of the modified BR (modified conjugated diene polymer) is preferably 0 to 5, more preferably 0 to 2. In this specification, the temporal stability is determined by the Mooney viscosity (ML 1+4 , 125°C) and calculated from the following formula. The smaller the value, the better the stability over time. Formula: [Mooney viscosity (ML) after storage in a thermostatic chamber at 90°C for 2 days] 1+4 , 125℃)]-[Mooney viscosity (ML 1+4 , 125℃)]

[0081] The glass transition temperature of the modified BR (modified conjugated diene polymer) is preferably -40°C or lower, more preferably -43°C or lower, even more preferably -46°C or lower, and particularly preferably -50°C or lower. On the other hand, there is no particular lower limit to the glass transition temperature. The glass transition temperature (Tg) of the modified BR is a value determined as the glass transition onset temperature by measuring the temperature at a heating rate of 10°C / min using a differential scanning calorimeter (Q200) manufactured by TA Instruments Japan in accordance with JIS K 7121.

[0082] As the BR, for example, products from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used.

[0083] In the rubber composition, the BR content is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. By keeping the BR content within the above range, the overall performance of fuel economy, abrasion resistance, and wet grip performance is significantly improved.

[0084] (Carbon Black) The rubber composition contains carbon black. As the carbon black, those generally used in tire manufacturing can be used, such as SAF, ISAF, HAF, FF, FEF, GPF, etc. These carbon blacks can be used alone or in combination of two or more kinds.

[0085] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 50 m 2 / g or more, more preferably 70m 2 / g or more, more preferably 85m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200m 2By making the N2SA of the carbon black equal to or higher than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or lower than the upper limit, good carbon black dispersibility and excellent fuel economy tend to be obtained. The N2SA of carbon black can be measured in accordance with JIS-K6217-2:2001.

[0086] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 50 ml / 100 g or more, more preferably 100 ml / 100 g or more, and even more preferably 110 ml / 100 g or more. The DBP is preferably 250 ml / 100 g or less, more preferably 200 ml / 100 g or less, and even more preferably 180 ml / 100 g or less. By setting it to the lower limit or more, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility is obtained, and excellent fuel efficiency tends to be obtained. The DBP of carbon black can be measured in accordance with JIS-K6217-4:2001.

[0087] From the viewpoint of overall performance, including fuel economy, abrasion resistance, and wet grip performance, carbon black having a compressed sample oil absorption of 100 to 180 ml / 100 g (hereinafter also referred to as "high structure carbon black") can also be suitably used as the carbon black.

[0088] The compressed oil absorption (COAN) of the high structure carbon black is 100 ml / 100 g or more, preferably 110 ml / 100 g or more, more preferably 120 ml / 100 g or more. The COAN is 180 ml / 100 g or less, preferably 170 ml / 100 g or less, more preferably 150 ml / 100 g or less. By keeping the COAN within the above range, good overall performance of low fuel consumption, wear resistance and wet grip performance tends to be obtained. In this specification, the COAN of carbon black is determined by the measurement method of JIS K6217-4. The oil used is dibutyl phthalate.

[0089] The nitrogen adsorption specific surface area (N2SA) of the high structure carbon black is preferably 100 m 2 / g or more, more preferably 150m 2 The nitrogen adsorption specific surface area is preferably 600 m 2 / g or less, more preferably 450m 2 / g or less, more preferably 300m 2 / g or less, particularly preferably 250m 2 By keeping the value within the above range, there is a tendency that good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance can be obtained.

[0090] The volatile content of the high structure carbon black at 900° C. is preferably 0.50% by mass or less, more preferably 0.46% by mass or less. By keeping it below the upper limit, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained. The lower limit of the volatile content is not particularly limited. In this specification, the volatile content of carbon black is determined by a measurement method in accordance with JIS K6221 (1994).

[0091] The volatile content of the high structure carbon black at 1500° C. is preferably 1.00% by mass or less, more preferably 0.70% by mass or less. By keeping it below the upper limit, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained. The lower limit of the volatile content is not particularly limited.

[0092] The pH of the high structure carbon black measured according to JIS K 6220-1 is preferably 6.0 or more, more preferably 7.0 or more, and even more preferably 8.5 or more. The pH is preferably 12.0 or less, more preferably 11.0 or less. By keeping the pH within the above range, good overall performance of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0093] As a method for producing high structure carbon black, a conventionally known method such as a furnace method or a channel method is used, and it can be produced, for example, by the method described in JP 2013-116940 A.

[0094] In the rubber composition, the content of carbon black is 30 parts by mass or more, preferably 35 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 45 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit of the content is not particularly limited, but is preferably 150 parts by mass or less, more preferably 120 parts by mass or less, and even more preferably 100 parts by mass or less. By making it equal to or more than the lower limit, good abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good fuel economy tends to be obtained.

[0095] (silica) From the viewpoint of overall performance, including fuel economy, abrasion resistance, and wet grip performance, the rubber composition preferably contains silica.

[0096] The silica is not particularly limited, and examples thereof include dry process silica (anhydrous silicic acid) and wet process silica (hydrated silicic acid). Wet process silica is preferred because it has many silanol groups.

[0097] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 80m 2 / g or more, more preferably 100m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained. The N2SA of silica can be measured in accordance with ASTM D3037-81.

[0098] As silica, nitrogen adsorption specific surface area (N2SA) N2SA160m 2 / g or more (hereinafter also referred to as "fine particle silica") can also be suitably used. The lower limit of N2SA of fine particle silica is 165 m 2 / g or more is preferable, and 170m 2 / g or more is more preferable. The upper limit is 300m 2 / g or less is preferable, and 250m 2 By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0099] In the rubber composition, the content of silica (total amount of various silicas) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 80 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less. By making the content equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making the content equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0100] In the rubber composition, the total content of carbon black and silica is preferably 20 parts by mass or more, more preferably 35 parts by mass or more, and even more preferably 40 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 120 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 70 parts by mass or less. By making the content equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making the content equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0101] (Silane coupling agent) When the rubber composition contains silica, it is preferable that the rubber composition contains a silane coupling agent together with the silica. The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N Examples of such silanes include sulfide-based silanes such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, vinyl-based silanes such as vinyltriethoxysilane, vinyltrimethoxysilane, amino-based silanes such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, glycidoxy-based silanes such as γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, nitro-based silanes such as 3-nitropropyltrimethoxysilane, 3-nitropropyltriethoxysilane, and chloro-based silanes such as 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane. As commercially available products, for example, products from Degussa, Momentive, Shin-Etsu Silicone Co., Ltd., Tokyo Chemical Industry Co., Ltd., Azumax Co., Ltd., Dow Corning Toray Co., Ltd., etc. can be used. These may be used alone or in combination of two or more kinds.Among these, from the viewpoint of overall performance including fuel economy, abrasion resistance, and wet grip performance, sulfide-based silane coupling agents and mercapto-based silane coupling agents are preferred, and mercapto-based silane coupling agents are more preferred.

[0102] Examples of the mercapto-based silane coupling agent include a silane coupling agent having a mercapto group, a silane coupling agent in which the mercapto group is protected, etc. These may be used alone or in combination of two or more kinds.

[0103] Suitable mercapto-based silane coupling agents include (i) a silane coupling agent represented by the following formula (2-1), and (ii) a silane coupling agent containing a bond unit A represented by the following formula (2-2) and a bond unit B represented by the following formula (2-3). [ka] (In formula (2-1), R 101 -Cl, -Br, -OR 106 , -O(O=)CR 106 , -ON=CR 106 R 107 , -ON=CR 106 R 107 , -NR 106 R 107 and-(OSiR 106 R 107 ) h (OSiR 106 R 107 R 108 ) a monovalent group (R 106 , R 107 and R 108 may be the same or different, each is a hydrogen atom or a monovalent hydrocarbon group having 1 to 18 carbon atoms, and h has an average value of 1 to 4; 102 is R 101 , a hydrogen atom or a monovalent hydrocarbon group having 1 to 18 carbon atoms, R 103 is -[O(R 109 O) j ]-group(R 109 is an alkylene group having 1 to 18 carbon atoms, and j is an integer of 1 to 4.104 is a divalent hydrocarbon group having 1 to 18 carbon atoms, R 105 represents a monovalent hydrocarbon group having 1 to 18 carbon atoms, and xa, ya, and za are numbers that satisfy the relationship: xa+ya+2za=3, 0≦xa≦3, 0≦ya≦2, 0≦za≦1. [ka] [ka] (In formulas (2-2) and (2-3), xb is an integer of 0 or more, and yb is an integer of 1 or more. R 201 R represents hydrogen, halogen, a branched or unbranched alkyl group having 1 to 30 carbon atoms, a branched or unbranched alkenyl group having 2 to 30 carbon atoms, a branched or unbranched alkynyl group having 2 to 30 carbon atoms, or an alkyl group in which the terminal hydrogen atom has been substituted with a hydroxyl group or a carboxyl group. 202 R represents a branched or unbranched alkylene group having 1 to 30 carbon atoms, a branched or unbranched alkenylene group having 2 to 30 carbon atoms, or a branched or unbranched alkynylene group having 2 to 30 carbon atoms. 201 and R 202 may form a ring structure.)

[0104] R in the above formula (2-1) 102 , R 105 , R 106 , R 107 and R 108 Specific examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, an octyl group, a decyl group, a dodecyl group, a cyclopentyl group, a cyclohexyl group, a vinyl group, a propenyl group, an allyl group, a hexenyl group, an octenyl group, a cyclopentenyl group, a cyclohexenyl group, a phenyl group, a tolyl group, a xylyl group, a naphthyl group, a benzyl group, a phenethyl group, and a naphthylmethyl group. R in the above formula (2-1) 109Examples of the linear alkylene group include a methylene group, an ethylene group, an n-propylene group, an n-butylene group, and a hexylene group, and examples of the branched alkylene group include an isopropylene group, an isobutylene group, and a 2-methylpropylene group.

[0105] Specific examples of the silane coupling agent represented by the above formula (2-1) include 3-hexanoylthiopropyl triethoxysilane, 3-octanoylthiopropyl triethoxysilane, 3-decanoylthiopropyl triethoxysilane, 3-lauroylthiopropyl triethoxysilane, 2-hexanoylthioethyl triethoxysilane, 2-octanoylthioethyl triethoxysilane, 2-decanoylthioethyl triethoxysilane, 2-lauroylthioethyl triethoxysilane, 3-hexanoylthiopropyl trimethoxysilane, 3-octanoylthiopropyl trimethoxysilane, 3-decanoylthiopropyl trimethoxysilane, 3-lauroylthiopropyl trimethoxysilane, 2-hexanoylthioethyl trimethoxysilane, 2-octanoylthioethyl trimethoxysilane, 2-decanoylthioethyl trimethoxysilane, and 2-lauroylthioethyl trimethoxysilane. Among these, 3-octanoylthiopropyltriethoxysilane (NXT manufactured by Momentive Corp.) is particularly preferred. The above silane coupling agents may be used alone or in combination of two or more kinds.

[0106] The silane coupling agent containing the bond unit A represented by the above formula (2-2) and the bond unit B represented by the above formula (2-3) shows less increase in viscosity during processing than polysulfide silanes such as bis-(3-triethoxysilylpropyl)tetrasulfide. This is thought to be because the sulfide portion of the bond unit A is a CSC bond, which is more thermally stable than tetrasulfides and disulfides, resulting in less increase in Mooney viscosity.

[0107] In addition, compared to mercaptosilanes such as 3-mercaptopropyltrimethoxysilane, the reduction in scorch time is suppressed. This is because the bond unit A has a mercaptosilane structure, but the -CH of the bond unit A 15 This is thought to be because the -SH group of the bonding unit B is covered by this moiety, making it less likely to react with the polymer and less likely to cause scorch.

[0108] In the silane coupling agent of the above structure, the content of the bond unit A is preferably 30 mol% or more, more preferably 50 mol% or more, and preferably 99 mol% or less, more preferably 90 mol% or less.In addition, the content of the bond unit B is preferably 1 mol% or more, more preferably 5 mol% or more, even more preferably 10 mol% or more, and preferably 70 mol% or less, more preferably 65 mol% or less, even more preferably 55 mol% or less, from the viewpoint of reactivity with silica.In addition, the total content of the bond units A and B is preferably 95 mol% or more, more preferably 98 mol% or more, and particularly preferably 100 mol%. The content of the bond units A and B includes the case where the bond units A and B are located at the terminals of the silane coupling agent. When the bond units A and B are located at the terminals of the silane coupling agent, the form is not particularly limited, and it is sufficient that they form units corresponding to the formulas (2-2) and (2-3) representing the bond units A and B.

[0109] R 201 Examples of the halogen include chlorine, bromine, and fluorine.

[0110] R 201 Examples of the branched or unbranched alkyl group having 1 to 30 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an iso-butyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, an octyl group, a nonyl group, a decyl group, etc. The number of carbon atoms of the alkyl group is preferably 1 to 12.

[0111] R 201Examples of the branched or unbranched alkenyl group having 2 to 30 carbon atoms include a vinyl group, a 1-propenyl group, a 2-propenyl group, a 1-butenyl group, a 2-butenyl group, a 1-pentenyl group, a 2-pentenyl group, a 1-hexenyl group, a 2-hexenyl group, a 1-octenyl group, etc. The number of carbon atoms of the alkenyl group is preferably 2 to 12.

[0112] R 201 Examples of the branched or unbranched alkynyl group having 2 to 30 carbon atoms include an ethynyl group, a propynyl group, a butynyl group, a pentynyl group, a hexynyl group, a heptynyl group, an octynyl group, a nonynyl group, a decynyl group, an undecynyl group, a dodecynyl group, etc. The number of carbon atoms of the alkynyl group is preferably 2 to 12.

[0113] R 202 Examples of the branched or unbranched alkylene group having 1 to 30 carbon atoms include an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, a heptylene group, an octylene group, a nonylene group, a decylene group, an undecylene group, a dodecylene group, a tridecylene group, a tetradecylene group, a pentadecylene group, a hexadecylene group, a heptadecylene group, an octadecylene group, etc. The number of carbon atoms of the alkylene group is preferably 1 to 12.

[0114] R 202 Examples of the branched or unbranched alkenylene group having 2 to 30 carbon atoms include a vinylene group, a 1-propenylene group, a 2-propenylene group, a 1-butenylene group, a 2-butenylene group, a 1-pentenylene group, a 2-pentenylene group, a 1-hexenylene group, a 2-hexenylene group, a 1-octenylene group, etc. The number of carbon atoms in the alkenylene group is preferably 2 to 12.

[0115] R 202 Examples of the branched or unbranched alkynylene group having 2 to 30 carbon atoms include an ethynylene group, a propynylene group, a butynylene group, a pentynylene group, a hexynylene group, a heptynylene group, an octynylene group, a nonynylene group, a decynylene group, an undecynylene group, a dodecynylene group, etc. The number of carbon atoms of the alkynylene group is preferably 2 to 12.

[0116] In a silane coupling agent containing a bonding unit A represented by formula (2-2) and a bonding unit B represented by formula (2-3), the total number of repetitions (xb+yb) of the bonding unit A and the bonding unit B is preferably in the range of 3 to 300. When it is in this range, the mercaptosilane of the bonding unit B is preferably -CH of the bonding unit A. 15 Since the rubber component is covered with the silica, the scorch time can be prevented from becoming shorter and good reactivity with the silica and rubber components can be ensured.

[0117] As the silane coupling agent containing the bond unit A represented by formula (2-2) and the bond unit B represented by formula (2-3), for example, NXT-Z30, NXT-Z45, NXT-Z60, etc. manufactured by Momentive Corp. can be used. These may be used alone or in combination of two or more kinds.

[0118] As the mercapto-based silane coupling agent, (iii) a silane coupling agent represented by the following formula (2-4) can also be suitably used.

[0119] [ka]

[0120] (In formula (2-4), R 6 ~R 8 represents a branched or unbranched alkyl group having 1 to 12 carbon atoms, a branched or unbranched alkoxy group having 1 to 12 carbon atoms, or -O-(R 10 -O) z -R 11 (z R 10 represents a branched or unbranched divalent hydrocarbon group having 1 to 30 carbon atoms. 10 may be the same or different. 11represents a branched or unbranched alkyl group having 1 to 30 carbon atoms, a branched or unbranched alkenyl group having 2 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an aralkyl group having 7 to 30 carbon atoms. z represents an integer of 1 to 30. R 6 ~R 8 may be the same or different. 9 represents a branched or unbranched alkylene group having 1 to 6 carbon atoms.

[0121] R 6 ~R 8 represents a branched or unbranched alkyl group having 1 to 12 carbon atoms, a branched or unbranched alkoxy group having 1 to 12 carbon atoms, or -O-(R 10 -O) z -R 11 R represents a group represented by the formula: 6 ~R 8 has at least one -O-(R 10 -O) z -R 11 Preferably, two of the groups are represented by -O-(R 10 -O) z -R 11 and one of them is a branched or unbranched alkoxy group having 1 to 12 carbon atoms.

[0122] R 6 ~R 8 Examples of the branched or unbranched alkyl group having 1 to 12 carbon atoms (preferably 1 to 5 carbon atoms) include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an iso-butyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, an octyl group, and a nonyl group.

[0123] R 6 ~R 8Examples of the branched or unbranched alkoxy group having 1 to 12 carbon atoms (preferably 1 to 5 carbon atoms) include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, an iso-butoxy group, a sec-butoxy group, a tert-butoxy group, a pentyloxy group, a hexyloxy group, a heptyloxy group, a 2-ethylhexyloxy group, an octyloxy group, and a nonyloxy group.

[0124] R 6 ~R 8 -O-(R 10 -O) z -R 11 In R 10 represents a branched or unbranched divalent hydrocarbon group having 1 to 30 carbon atoms (preferably 1 to 15 carbon atoms, more preferably 1 to 3 carbon atoms). Examples of the hydrocarbon group include a branched or unbranched alkylene group having 1 to 30 carbon atoms, a branched or unbranched alkenylene group having 2 to 30 carbon atoms, a branched or unbranched alkynylene group having 2 to 30 carbon atoms, and an arylene group having 6 to 30 carbon atoms. Among these, a branched or unbranched alkylene group having 1 to 30 carbon atoms is preferred.

[0125] R 10 Examples of the branched or unbranched alkylene group having 1 to 30 carbon atoms (preferably 1 to 15 carbon atoms, more preferably 1 to 3 carbon atoms) include a methylene group, ethylene group, propylene group, butylene group, pentylene group, hexylene group, heptylene group, octylene group, nonylene group, decylene group, undecylene group, dodecylene group, tridecylene group, tetradecylene group, pentadecylene group, hexadecylene group, heptadecylene group, and octadecylene group.

[0126] R 10Examples of the branched or unbranched alkenylene group having 2 to 30 carbon atoms (preferably 2 to 15 carbon atoms, more preferably 2 to 3 carbon atoms) include a vinylene group, a 1-propenylene group, a 2-propenylene group, a 1-butenylene group, a 2-butenylene group, a 1-pentenylene group, a 2-pentenylene group, a 1-hexenylene group, a 2-hexenylene group, and a 1-octenylene group.

[0127] R 10 Examples of the branched or unbranched alkynylene group having 2 to 30 carbon atoms (preferably having 2 to 15 carbon atoms, more preferably having 2 to 3 carbon atoms) include an ethynylene group, a propynylene group, a butynylene group, a pentynylene group, a hexynylene group, a heptynylene group, an octynylene group, a nonynylene group, a decynylene group, an undecynylene group, and a dodecynylene group.

[0128] R 10 Examples of the arylene group having 6 to 30 carbon atoms (preferably 6 to 15 carbon atoms) include a phenylene group, a tolylene group, a xylylene group, and a naphthylene group.

[0129] z represents an integer of 1 to 30 (preferably 2 to 20, more preferably 3 to 7, and further preferably 5 to 6).

[0130] R 11 represents a branched or unbranched alkyl group having 1 to 30 carbon atoms, a branched or unbranched alkenyl group having 2 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an aralkyl group having 7 to 30 carbon atoms. Among these, a branched or unbranched alkyl group having 1 to 30 carbon atoms is preferred.

[0131] R 11Examples of the branched or unbranched alkyl group having 1 to 30 carbon atoms (preferably 3 to 25 carbon atoms, more preferably 10 to 15 carbon atoms) include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an iso-butyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, and an octadecyl group.

[0132] R 11 Examples of the branched or unbranched alkenyl group having 2 to 30 carbon atoms (preferably 3 to 25 carbon atoms, more preferably 10 to 15 carbon atoms) include a vinyl group, a 1-propenyl group, a 2-propenyl group, a 1-butenyl group, a 2-butenyl group, a 1-pentenyl group, a 2-pentenyl group, a 1-hexenyl group, a 2-hexenyl group, a 1-octenyl group, a decenyl group, an undecenyl group, a dodecenyl group, a tridecenyl group, a tetradecenyl group, a pentadecenyl group, and an octadecenyl group.

[0133] R 11 Examples of the aryl group having 6 to 30 carbon atoms (preferably 10 to 20 carbon atoms) include a phenyl group, a tolyl group, a xylyl group, a naphthyl group, and a biphenyl group.

[0134] R 11 Examples of the aralkyl group having 7 to 30 carbon atoms (preferably 10 to 20 carbon atoms) include a benzyl group and a phenethyl group.

[0135] -O-(R 10 -O) z -R 11 Specific examples of the group represented by the formula are, for example, -O-(C2H4-O)5-C 11 H 23 , -O-(C2H4-O)5-C 12 H 25 , -O-(C2H4-O)5-C 13 H 27 , -O-(C2H4-O)5-C 14 H 29, -O-(C2H4-O)5-C 15 H 31 , -O-(C2H4-O)3-C 13 H 27 , -O-(C2H4-O)4-C 13 H 27 , -O-(C2H4-O)6-C 13 H 27 , -O-(C2H4-O)7-C 13 H 27 Among them, -O-(C2H4-O)5-C 11 H 23 , -O-(C2H4-O)5-C 13 H 27 , -O-(C2H4-O)5-C 15 H 31 , -O-(C2H4-O)6-C 13 H 27 is preferred.

[0136] R 9 Examples of the branched or unbranched alkylene group having 1 to 6 carbon atoms (preferably 1 to 5 carbon atoms) include R 10 Examples of the branched or unbranched alkylene group having 1 to 30 carbon atoms include the same groups as those mentioned above.

[0137] Examples of the compound represented by the above formula (2-4) include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and the compound represented by the following formula (Si363 manufactured by EVONIK-DEGUSSA), and the compound represented by the following formula can be preferably used. These may be used alone or in combination of two or more kinds. [ka]

[0138] When the rubber composition contains a silane coupling agent, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of silica. The content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By making the content equal to or more than the lower limit, the effect of improving dispersibility tends to be sufficiently obtained. By making the content equal to or less than the upper limit, the coupling effect tends to be sufficient, and good reinforcement tends to be obtained.

[0139] (Liquid plasticizer) The rubber composition may be blended with a liquid plasticizer (a plasticizer that is in a liquid state at room temperature (25° C.)). The liquid plasticizer is not particularly limited, but examples thereof include oil, liquid polymer (liquid diene-based polymer), liquid resin, etc. One type of these may be used, or two or more types may be used in combination. Among these, oil, liquid polymer, and liquid resin are preferred, and oil is particularly preferred from the viewpoint of processability, etc.

[0140] From an environmental perspective, the liquid plasticizer preferably has a polycyclic aromatic content (PCA) of less than 3% by mass, more preferably less than 1% by mass, as measured according to the British Petroleum Institute 346 / 92 method.

[0141] The oil is not particularly limited, and may be any conventionally known oil, such as paraffin-based process oil, aromatic process oil, naphthenic process oil, low PCA (polycyclic aromatic) process oil such as TDAE and MES, vegetable oil, and mixtures thereof. Among them, aromatic process oil is preferred in terms of rubber properties. Specific examples of the aromatic process oil include Diana Process Oil AH series manufactured by Idemitsu Kosan Co., Ltd.

[0142] The liquid polymer (liquid diene polymer) may be a diene polymer that is in a liquid state at room temperature (25° C.). The liquid diene polymer has a weight average molecular weight (Mw) of 1.0×10 based on polystyrene standards, as measured by gel permeation chromatography (GPC). 3 ~2.0×10 5 Preferably, it is 3.0×10 3 ~1.5×10 4 It is more preferable that:

[0143] Examples of liquid diene polymers include liquid styrene-butadiene copolymer (liquid SBR), liquid butadiene polymer (liquid BR), liquid isoprene polymer (liquid IR), and liquid styrene-isoprene copolymer (liquid SIR).

[0144] The liquid resin is not particularly limited, but examples thereof include liquid aromatic vinyl polymers, coumarone-indene resins, indene resins, terpene resins, rosin resins, and hydrogenated products thereof.

[0145] Examples of the liquid aromatic vinyl polymer include resins obtained by polymerizing α-methylstyrene and / or styrene, etc. Specific examples include liquid resins such as homopolymers of styrene, homopolymers of α-methylstyrene, and copolymers of α-methylstyrene and styrene.

[0146] The liquid coumarone-indene resin may be a resin containing coumarone and indene as the main monomer components constituting the resin skeleton (main chain). Other monomer components that may be contained in the skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.

[0147] Examples of liquid indene resins include liquid resins containing indene as a main monomer component constituting the skeleton (main chain) of the resin.

[0148] Examples of liquid terpene resins include resins obtained by polymerizing terpene compounds such as α-pinene, β-pinene, camphor, and dipentene, and liquid terpene resins such as terpene phenol, which is a resin obtained using a terpene compound and a phenolic compound as raw materials.

[0149] Examples of liquid rosin resins include liquid rosin-based resins such as natural rosin, polymerized rosin, modified rosin, ester compounds thereof, and hydrogenated products thereof.

[0150] In the rubber composition, the content of the liquid plasticizer is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, good processability tends to be obtained. Moreover, the content is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less. By making it equal to or less than the upper limit, good abrasion resistance, wet grip performance, and the like tend to be obtained. The content of the liquid plasticizer also includes the amount of oil (extending oil) contained in the rubber (oil-extended rubber). The content of the oil is also preferably within a similar range.

[0151] (Solid Resin) The rubber composition may contain a solid resin (a polymer in a solid state at room temperature (25° C.)). The solid resin is not particularly limited, but examples thereof include solid styrene-based resins, coumarone-indene resins, terpene-based resins, pt-butylphenol acetylene resins, acrylic-based resins, dicyclopentadiene-based resins (DCPD-based resins), C5-based petroleum resins, C9-based petroleum resins, and C5C9-based petroleum resins. These may be used alone or in combination of two or more.

[0152] The solid styrene-based resin is a solid polymer using a styrene-based monomer as a constituent monomer, and examples thereof include polymers polymerized with a styrene-based monomer as the main component (50% by mass or more).Specific examples thereof include homopolymers obtained by polymerizing each of the styrene-based monomers (styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, p-phenylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, etc.) alone, copolymers obtained by copolymerizing two or more kinds of styrene-based monomers, and copolymers of a styrene-based monomer and another monomer that can be copolymerized therewith.

[0153] Examples of the other monomers include acrylonitriles such as acrylonitrile and methacrylonitrile, unsaturated carboxylic acids such as acrylics and methacrylic acid, unsaturated carboxylic acid esters such as methyl acrylate and methyl methacrylate, dienes such as chloroprene and butadiene-isoprene, olefins such as 1-butene and 1-pentene, α,β-unsaturated carboxylic acids or acid anhydrides thereof such as maleic anhydride, and the like.

[0154] Among these, solid α-methylstyrene-based resins (such as α-methylstyrene homopolymers and copolymers of α-methylstyrene and styrene) are preferred.

[0155] The solid coumarone-indene resin may be a solid resin having the same constitutional units as the above-mentioned liquid coumarone-indene resin.

[0156] Examples of solid terpene resins include polyterpene, terpene phenol, and aromatic modified terpene resins. Polyterpenes are resins obtained by polymerizing terpene compounds and their hydrogenated products. Terpene compounds are (C5H8) n The hydrocarbons and their oxygen-containing derivatives represented by the composition 10 H 16 ), sesquiterpenes (C 15 H 24), diterpenes (C 20 H 32 ), and examples thereof include α-pinene, β-pinene, dipentene, limonene, myrcene, alloocimene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinolene, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, and γ-terpineol.

[0157] Examples of solid polyterpenes include terpene resins such as α-pinene resin, β-pinene resin, limonene resin, dipentene resin, and β-pinene / limonene resin, which are made from the above-mentioned terpene compounds as raw materials, as well as solid resins such as hydrogenated terpene resins obtained by hydrogenating the terpene resins.

[0158] The solid terpene phenol includes the solid resin obtained by copolymerizing the above-mentioned terpene compound with a phenolic compound, and the solid resin obtained by hydrogenating the above-mentioned resin, and specifically includes the solid resin obtained by condensing the above-mentioned terpene compound, a phenolic compound, and formalin.The phenolic compound includes, for example, phenol, bisphenol A, cresol, xylenol, etc.

[0159] The solid aromatic modified terpene resin includes the solid resin obtained by modifying terpene resin with aromatic compound, and the solid resin obtained by hydrogenating the resin.The aromatic compound is not particularly limited as long as it is a compound having an aromatic ring, and includes, for example, phenolic compounds such as phenol, alkylphenol, alkoxyphenol, and unsaturated hydrocarbon group-containing phenol; naphthol compounds such as naphthol, alkylnaphthol, alkoxynaphthol, and unsaturated hydrocarbon group-containing naphthol; styrene derivatives such as styrene, alkylstyrene, alkoxystyrene, and unsaturated hydrocarbon group-containing styrene; coumarone, indene, etc.

[0160] The solid pt-butylphenol acetylene resin may be a solid resin obtained by subjecting pt-butylphenol to a condensation reaction with acetylene.

[0161] The solid acrylic resin is not particularly limited, but a solventless acrylic solid resin can be preferably used because it contains few impurities and has a sharp molecular weight distribution.

[0162] Examples of solid solvent-free acrylic resins include (meth)acrylic resins (polymers) synthesized by high-temperature continuous polymerization (high-temperature continuous bulk polymerization) (methods described in U.S. Pat. No. 4,414,370, JP-A-59-6207, JP-B-5-58005, JP-A-1-313522, U.S. Pat. No. 5,010,166, and Toa Gosei Kenkyuu Nenpo TREND 2000 Vol. 3, p. 42-45, etc.) using minimal use of auxiliary raw materials such as polymerization initiators, chain transfer agents, and organic solvents. In this specification, (meth)acrylic means methacryl and acrylic.

[0163] The solid acrylic resin preferably does not substantially contain auxiliary materials such as a polymerization initiator, a chain transfer agent, an organic solvent, etc. In addition, the acrylic resin is preferably one obtained by continuous polymerization and has a relatively narrow composition distribution and molecular weight distribution.

[0164] As described above, the solid acrylic resin is preferably one that does not substantially contain auxiliary materials such as a polymerization initiator, a chain transfer agent, an organic solvent, etc., that is, one with high purity. The purity of the solid acrylic resin (the proportion of the resin contained in the resin) is preferably 95% by mass or more, more preferably 97% by mass or more.

[0165] Examples of monomer components constituting a solid acrylic resin include (meth)acrylic acid, (meth)acrylic acid esters (alkyl esters, aryl esters, aralkyl esters, etc.), (meth)acrylamide, and (meth)acrylic acid derivatives such as (meth)acrylamide derivatives.

[0166] In addition, aromatic vinyls such as styrene, α-methylstyrene, vinyltoluene, vinylnaphthalene, divinylbenzene, trivinylbenzene, and divinylnaphthalene may be used together with (meth)acrylic acid or a (meth)acrylic acid derivative as a monomer component constituting a solid acrylic resin.

[0167] The solid acrylic resin may be a resin composed only of a (meth)acrylic component, or a resin containing components other than the (meth)acrylic component as constituent elements. The solid acrylic resin may have a hydroxyl group, a carboxyl group, a silanol group, or the like.

[0168] In the rubber composition, the content of the solid resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. When the content is within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0169] Examples of liquid plasticizers and solid resins that can be used include products from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Nitto Chemical Co., Ltd., Nippon Shokubai Co., Ltd., JXTG Nippon Oil & Energy Corporation, Arakawa Chemical Industries, Ltd., and Taoka Chemical Co., Ltd.

[0170] (Farnesene resin) The rubber composition preferably contains a farnesene-based resin. The farnesene-based resin means a polymer obtained by polymerizing farnesene as a monomer component. Farnesene has isomers such as α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecatetraene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecatriene), but (E)-β-farnesene having the following structure is preferred. [ka]

[0171] The farnesene-based resin may be a homopolymer of farnesene (farnesene homopolymer) or a copolymer of farnesene and a vinyl monomer (farnesene-vinyl monomer copolymer). Examples of vinyl monomers include aromatic vinyl compounds such as styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 4-tert-butylstyrene, 5-t-butyl-2-methylstyrene, vinylethylbenzene, divinylbenzene, trivinylbenzene, divinylnaphthalene, tert-butoxystyrene, vinylbenzyldimethylamine, (4-vinylbenzyl)dimethylaminoethylether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-t-butylstyrene, 3-t-butylstyrene, 4-t-butylstyrene, vinylxylene, vinylnaphthalene, vinyltoluene, vinylpyridine, diphenylethylene, and tertiary amino group-containing diphenylethylene, as well as conjugated diene compounds such as butadiene and isoprene. Among these, styrene and butadiene are preferred. That is, as the farnesene-vinyl monomer copolymer, a copolymer of farnesene and styrene (farnesene-styrene copolymer) and a copolymer of farnesene and butadiene (farnesene-butadiene copolymer) are preferable. By blending the farnesene-styrene copolymer, it is possible to enhance the improving effect of breaking strength, steering stability, wet grip performance and abrasion resistance, and by blending the farnesene-butadiene copolymer, it is possible to enhance the improving effect of fuel economy and abrasion resistance.

[0172] The farnesene homopolymer has a glass transition temperature (Tg) of preferably −60° C. or lower, more preferably −70° C. or lower, and preferably −120° C. or higher, more preferably −110° C. or higher. Within the above range, it can be suitably used as a tire softener. For the same reason, the Tg of the farnesene-styrene copolymer is preferably −15° C. or lower, more preferably −30° C. or lower, and is preferably −80° C. or higher, more preferably −70° C. or higher. For the same reason, the Tg of the farnesene-butadiene copolymer is preferably −60° C. or lower, more preferably −70° C. or lower, and is preferably −120° C. or higher, more preferably −110° C. or higher. In this specification, the Tg of the farnesene resin is a value measured in accordance with JIS-K7121:1987 using a differential scanning calorimeter (Q200) manufactured by TA Instruments Japan at a heating rate of 10°C / min.

[0173] The weight average molecular weight (Mw) of the farnesene homopolymer is preferably 3000 or more, more preferably 5000 or more, and even more preferably 8000 or more. If it is 3000 or more, the steering stability and abrasion resistance tend to be improved. Moreover, the Mw is preferably 500000 or less, more preferably 300000 or less, and even more preferably 150000 or less. If it is 500000 or less, the processability and abrasion resistance tend to be improved. In addition, the Mw of the farnesene-vinyl monomer copolymer is preferably 3000 or more, more preferably 5000 or more, and even more preferably 8000 or more. If it is 3000 or more, the steering stability performance tends to improve. In addition, the Mw is preferably 500000 or less, more preferably 300000 or less, even more preferably 150000 or less, and particularly preferably 100000 or less. If it is 500000 or less, the wet grip performance tends to improve. The farnesene homopolymer and farnesene-vinyl monomer copolymer having Mw within the above range are liquid at room temperature and can be suitably used as a tire softener.

[0174] The melt viscosity of the farnesene homopolymer is preferably 1000 Pa s or less, more preferably 200 Pa s or less, and is preferably 0.1 Pa s or more, more preferably 0.5 Pa s or more. Within the above range, the farnesene homopolymer can be suitably used as a tire softener and has excellent bloom resistance. For the same reason, the melt viscosity of the farnesene-vinyl monomer copolymer is preferably 1000 Pa·s or less, more preferably 650 Pa·s or less, even more preferably 200 Pa·s or less, and is preferably 1 Pa·s or more, more preferably 5 Pa·s or more. In this specification, the melt viscosity of the farnesene resin is a value measured at 38° C. using a Brookfield viscometer (manufactured by BROOKFIELD ENGINEERING LABS. INC.).

[0175] In the farnesene homopolymer, the content of farnesene in 100% by mass of the monomer components is preferably 80% by mass or more, more preferably 90% by mass or more, and may be 100% by mass.

[0176] In the farnesene-vinyl monomer copolymer, the total content of farnesene and vinyl monomer in 100% by mass of the monomer components is preferably 80% by mass or more, more preferably 90% by mass or more, and may be 100% by mass. The copolymerization ratio of farnesene to vinyl monomer is preferably farnesene:vinyl monomer=99 / 1 to 25 / 75, and more preferably farnesene:vinyl monomer=80 / 20 to 40 / 60, based on mass.

[0177] Farnesene-based resins are commercially available, and for example, products available from Kuraray Co., Ltd. can be used.

[0178] In the rubber composition, the content of the farnesene resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. When the content is 1 part by mass or more, the performance improvement effect obtained by compounding the farnesene resin tends to be sufficiently obtained. In addition, the content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 20 parts by mass or less. When the content is 50 parts by mass or less, good fuel economy, wear resistance, wet grip performance, etc. tend to be obtained.

[0179] (Tetrazine compounds) The rubber composition may contain a tetrazine compound represented by the following general formula (1). [ka] [In the formula, R 1 and R 2 may be the same or different, each represents a hydrogen atom (-H), -COOR 3 (R 3 represents a hydrogen atom (-H) or an alkyl group) or a monovalent hydrocarbon group having 1 to 11 carbon atoms, and the hydrocarbon group may have a heteroatom. 1 and R 2 may form a salt.

[0180] Examples of the heteroatom include a nitrogen atom, an oxygen atom, and a sulfur atom. R 1 and R 2 The hydrocarbon group has 1 to 11 carbon atoms, preferably 2 to 9 carbon atoms, and more preferably 4 to 7 carbon atoms.

[0181] R 1 and R 2 As for the reason that it is thought that interactions with reinforcing fillers (especially carbon black and silica) are likely to occur, -COOR 3 or a hydrocarbon group having a hetero atom is preferred, and R 1 and R 2More preferably, both of are hydrocarbon groups having a heteroatom.

[0182] R 1 and R 2 The hydrocarbon group is not particularly limited, but is preferably a monocyclic group or a heterocyclic group, more preferably at least one of which is a heterocyclic group, and even more preferably both of which are heterocyclic groups, because such groups are thought to easily interact with a reinforcing filler (particularly, carbon black or silica). In this specification, a monocyclic group refers to a group whose ring structure is composed only of carbon atoms, and a heterocyclic group refers to a group whose ring structure is composed of two or more elements including carbon atoms.

[0183] Examples of the monocyclic group include an aryl group and a cycloalkyl group. Among these, an aryl group is preferable.

[0184] Examples of the aryl group include a phenyl group and a naphthyl group. Of these, a phenyl group is preferable.

[0185] Examples of the cycloalkyl group include a cyclopentyl group and a cyclohexyl group.

[0186] As the heterocyclic group, a nitrogen-containing heterocyclic group containing a nitrogen atom as a heteroatom constituting the ring is preferred, and a nitrogen-containing heterocyclic group containing only a nitrogen atom as a heteroatom constituting the ring is more preferred.

[0187] Examples of the nitrogen-containing heterocyclic group include an aziridinyl group, an azetidinyl group, a pyrrolidinyl group, a piperidinyl group, a hexamethyleneimino group, an imidazolidyl group, a piperazinyl group, a pyrazolidyl group, a pyrrolyl group, an imidazolyl group, a pyrazolyl group, a pyridyl group, a pyridazyl group, a pyrimidyl group, a pyrazyl group, a quinolyl group, an isoquinolyl group, a cinnolinyl group, a quinazolinyl group, a phthalazinyl group, etc. Among these, a pyridyl group and a pyrimidyl group are preferred, and a pyridyl group is more preferred.

[0188] The hydrogen atoms of the above-mentioned monocyclic group and heterocyclic group may be substituted with a substituent, and are preferably substituted with a substituent because it is believed that such substitution facilitates interaction with a reinforcing filler (particularly carbon black and silica).

[0189] Examples of the substituent include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, an epoxy group, a sulfonic acid group, and a trifluoromethyl group. These substituents may further have the above-mentioned substituents, and may have, for example, an alkylene group, an alkyl group, and the like in addition to the above-mentioned substituents. Among them, a carboxyl group, the above-mentioned -COOR 3 Preferred are an amino group (preferably a group represented by the following formula (A) or a group represented by the following formula (B)), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), and an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms). [ka]

[0190] The substituent may form a salt, like the groups represented by the above formulae (A) and (B). Examples of salts include salts of an amino group and a halogen atom, salts of a carboxyl group and a monovalent metal such as Na or K, and salts of a sulfonic acid group and the above monovalent metals.

[0191] Above - COOR 3 R 3 represents a hydrogen atom or an alkyl group. The alkyl group preferably has 1 to 8 carbon atoms, and more preferably 1 to 3 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, and a tert-butyl group. R 3 As the alkyl group, an alkyl group is preferable.

[0192] The tetrazine-based compound represented by the above general formula (1) is not particularly limited as long as it can react with diene rubber. The tetrazine-based compound may be used alone or in combination of two or more. Among them, the compound represented by the following general formula (1-1), (1-2), (1-3), or (1-4) (particularly, the compound represented by the following general formula (1-1) or (1-4)) is preferred, and the compound represented by the following formula (1-1-1), (1-1-2), (1-2-1), (1-3-1), (1-4-1) or (1-4-2) (particularly, the compound represented by the following formula (1-1-1) or (1-4-1)) is more preferred. The tetrazine compound represented by the above general formula (1) may be a commercially available product or may be synthesized by a known method. [ka] [In formula (1-1), R 11 is a hydrogen atom (-H), -COOR 17 (R 17 represents a hydrogen atom (-H) or an alkyl group) or a monovalent hydrocarbon group having 1 to 11 carbon atoms, and the hydrocarbon group may have a heteroatom. 11 may form a salt. [In formula (1-2), R 12 represents a functional group containing at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, a sulfur atom, a fluorine atom, and a silicon atom. 12 may form a salt. [In formula (1-3), R 13 and R 14 may be the same or different, and each represents a hydrogen atom (-H) or an alkyl group. 13 and R 14 may form a salt. [In formula (1-4), R15 and R 16 may be the same or different, each represents a hydrogen atom (-H), -COOR 18 (R 18 represents a hydrogen atom (-H) or an alkyl group, or a functional group containing at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, a sulfur atom, a fluorine atom, and a silicon atom. 15 and R 16 may form a salt. [ka]

[0193] R 11 The heteroatom in 1 and R 2 The heteroatoms in the above formula are similar to those in the above formula. R 11 The number of carbon atoms in the hydrocarbon group is R 1 and R 2 The preferred embodiments are also the same as those of the hydrocarbon group of the above.

[0194] R 11 As for the reason that it is thought that interactions with reinforcing fillers (especially carbon black and silica) are likely to occur, -COOR 17 Alternatively, a hydrocarbon group having a hetero atom is preferred.

[0195] R 11 As the hydrocarbon group of R 1 and R 2 The preferred embodiments are also the same as those of the hydrocarbon group in the above.

[0196] Above - COOR 17 R 17 represents a hydrogen atom or an alkyl group. The alkyl group is, for example, R 3 The alkyl group may be the same as the alkyl group in the above, and the preferred embodiments are also the same. R 17 As the alkyl group, an alkyl group is preferable.

[0197] R 12Examples of the functional group containing at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, a sulfur atom, a fluorine atom and a silicon atom include the same groups as the above-mentioned substituents, and preferred embodiments are also the same.

[0198] R 12 Although the position may be any of the ortho-, meta-, and para-positions, the para-position is preferred because the effects of the present invention can be more suitably obtained.

[0199] R 13 and R 14 The alkyl group of R 3 The alkyl group may be the same as the alkyl group of R. 13 and R 14 As the alkyl group, an alkyl group is preferable.

[0200] R 15 and R 16 is preferably a hydrogen atom or a functional group containing at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, a sulfur atom, a fluorine atom and a silicon atom.

[0201] -COOR 18 R 18 represents a hydrogen atom or an alkyl group. The alkyl group is, for example, R 3 The alkyl group may be the same as the alkyl group in the above, and the preferred embodiments are also the same. R 18 As the alkyl group, an alkyl group is preferable.

[0202] R 15 and R 16 Examples of the functional group containing at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, a sulfur atom, a fluorine atom and a silicon atom include the same groups as the above-mentioned substituents, and preferred embodiments are also the same.

[0203] R 15 and R 16 may be at any of the ortho, meta, and para positions, but is preferably at the para position; R 15 and R 16For both, the para position is more preferable.

[0204] In the rubber composition, the content of the tetrazine-based compound (total amount of the tetrazine-based compound) is preferably 0.2 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, good overall performance of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0205] (fine particle zinc carrier) The rubber composition may contain a particulate zinc carrier in which zinc oxide fine particles or basic zinc carbonate fine particles are supported on the surface of silicate particles.

[0206] The zinc particulate carrier is a silicate particle having zinc oxide or basic zinc carbonate particles supported on its surface. The silicate particle surface has an affinity for zinc oxide and basic zinc carbonate particles, and therefore the zinc oxide or basic zinc carbonate particles can be supported uniformly on the silicate particle surface.

[0207] The amount of zinc oxide microparticles or basic zinc carbonate microparticles supported is preferably in the range of 6 to 75 mass % in terms of metallic zinc, with the lower limit being more preferably 15 mass % or more, even more preferably 25 mass % or more, and particularly preferably 35 mass % or more, and the upper limit being more preferably 65 mass % or less, and even more preferably 55 mass % or less. Here, the supported amount in terms of metallic zinc can be calculated by calculating the mass of the supported zinc oxide fine particles or basic zinc carbonate fine particles converted into metallic zinc in terms of Zn, and using this value to calculate from the following formula. Amount of zinc supported (mass%) in terms of metallic zinc = (mass of zinc in terms of Zn) / (mass of fine particle zinc support) x 100

[0208] The BET specific surface area of ​​silicate particles carrying zinc oxide particles (zinc particle carrier) is 10 to 55 m 2 / g, and more preferably 15 to 50 m 2 / g, more preferably 20 to 45 m 2 / g range.

[0209] The BET specific surface area of ​​silicate particles carrying basic zinc carbonate particles (fine zinc particles carrying material) is 25 to 90 m 2 / g, and more preferably 30 to 85 m 2 / g, more preferably 35 to 80m 2 / g range.

[0210] The BET specific surface area can be determined by a nitrogen adsorption method using a BET specific surface area measuring device. Zn ) can be calculated using the following formula:

[0211] BET Zn ={(BET Zn-Si ×W Zn )+W Si (BET Zn-Si -BET Si )} / W Zn BET Zn-Si : BET specific surface area of ​​fine particle zinc support BET Si : BET specific surface area of ​​silicate particles W Zn % by mass of zinc oxide or basic zinc carbonate contained in the fine particle zinc carrier W Si % by mass of silicate particles contained in the fine particle zinc carrier

[0212] The BET specific surface area (BET Zn ) is 15 to 100 m for zinc oxide particles. 2 / g is preferable, and 40 to 80m 2 / g is more preferable, and in the case of basic zinc carbonate fine particles, it is 15 to 100 m 2 / g is preferable, and 40 to 80m 2 / g range is more preferred.

[0213] As the silicate particles, aluminum silicate mineral particles are preferably used. Examples of silicate particles other than aluminum silicate mineral particles include talc, mica, feldspar, bentonite, magnesium silicate, silica, calcium silicate (wollastonite), and diatomaceous earth.

[0214] The aluminum silicate mineral particles include, for example, at least one selected from kaolinite, halloysite, pyrophyllite, and sericite.

[0215] The aluminum silicate mineral particles are preferably anhydrous aluminum silicate mineral particles. Examples of the anhydrous aluminum silicate mineral particles include those obtained by firing at least one selected from kaolinite, halloysite, pyrophyllite, and sericite. For example, those obtained by firing these clay minerals consisting of fine particles with a particle size of 2 μm or less at a content rate of 80% or more at a temperature of 500 to 900° C. are included.

[0216] The zinc-supported fine particles can be produced, for example, by the method described in JP 2018-184497 A. Commercially available zinc-supported fine particles include products from Shiraishi Calcium Co., Ltd.

[0217] In the rubber composition, the content of the zinc microparticle carrier is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.6 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 2.0 parts by mass or less, more preferably 1.8 parts by mass or less, and even more preferably 1.6 parts by mass or less. By keeping the content within the above range, good overall performance of fuel economy, wear resistance, and wet grip performance tends to be obtained.

[0218] (Amide compounds) The rubber composition preferably contains an amide compound. The amide compound is not particularly limited, but may be fatty acid amide or fatty acid amide ester. The amide compound may be used alone or in combination of two or more. Among them, fatty acid amide is preferred, and a mixture of fatty acid amide and fatty acid amide ester is more preferred.

[0219] The fatty acid amide may be a saturated fatty acid amide or an unsaturated fatty acid amide. Examples of the saturated fatty acid amide include stearic acid amide and behenic acid amide, and examples of the unsaturated fatty acid amide include oleic acid amide and erucic acid amide. Among these, unsaturated fatty acid amide is preferred, and oleic acid amide is more preferred.

[0220] The fatty acid amide ester may be a saturated fatty acid amide ester or an unsaturated fatty acid amide ester. Examples of the saturated fatty acid amide ester include stearic acid amide ester and behenic acid amide ester, and examples of the unsaturated fatty acid amide ester include oleic acid amide ester and erucic acid amide ester. These may be used alone or in combination of two or more. Among them, unsaturated fatty acid amide ester is preferred, and oleic acid amide ester is more preferred.

[0221] As the amide compound, a mixture of an amide compound and a fatty acid metal salt can also be suitably used. Examples of metals constituting fatty acid metal salts include potassium, sodium, magnesium, calcium, barium, zinc, nickel, molybdenum, etc. Among these, alkaline earth metals such as calcium and zinc are preferred, and calcium is more preferred.

[0222] The fatty acid constituting the fatty acid metal salt may be a saturated fatty acid or an unsaturated fatty acid. Examples of the saturated fatty acid include decanoic acid, dodecanoic acid, and stearic acid, and examples of the unsaturated fatty acid include oleic acid and elaidic acid. Among them, the saturated fatty acid is preferred, and stearic acid is more preferred. Also, the unsaturated fatty acid is preferred, and oleic acid is preferred.

[0223] As the amide compound, for example, products available from NOF Corporation, Struktol, LANXESS, etc. can be used.

[0224] In the rubber composition, the content of the amide compound relative to 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and also preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less. By keeping the content within the above range, there is a tendency to obtain good overall performance in terms of fuel economy, wear resistance, and wet grip performance. In this specification, when a mixture containing a fatty acid metal salt in addition to the amide compound is used as the amide compound, the content of the amide compound means the amount including the fatty acid metal salt.

[0225] (sulfur) The rubber composition preferably contains sulfur. Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. These may be used alone or in combination of two or more kinds.

[0226] As sulfur, for example, products from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanritsu Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. can be used.

[0227] In the rubber composition, the content of sulfur is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, and even more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0228] (Vulcanization accelerator) The rubber composition preferably contains a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenyl guanidine, di-orthotolyl guanidine, and orthotolyl biguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide vulcanization accelerators and guanidine vulcanization accelerators are preferred.

[0229] In the rubber composition, the content of the vulcanization accelerator is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, and even more preferably 2.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 5.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance can be obtained.

[0230] (Other ingredients) The rubber composition may contain a wax. The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as vegetable wax and animal wax; and synthetic waxes such as polymers of ethylene, propylene, etc. These may be used alone or in combination of two or more. Among them, petroleum waxes are preferred, and paraffin wax is more preferred.

[0231] As the wax, for example, products available from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Seiko Chemical Co., Ltd., etc. can be used.

[0232] The amount of the wax per 100 parts by mass of the rubber component is preferably 0.3 part by mass or more, more preferably 0.5 part by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less.

[0233] The rubber composition may contain an antioxidant. Examples of the antioxidant include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine. Examples of the antioxidant include p-phenylenediamine antioxidants such as quinolinone; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. Commercially available products include those from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and Flexis Co., Ltd. These may be used alone or in combination of two or more. Among them, p-phenylenediamine antioxidants and quinoline antioxidants are preferred.

[0234] The amount of the antioxidant per 100 parts by mass of the rubber component is preferably 0.5 part by mass or more, more preferably 1 part by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less.

[0235] The rubber composition may contain stearic acid. As the stearic acid, any conventionally known product can be used, for example, products available from NOF Corporation, NOF Corporation, Kao Corporation, Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., and the like.

[0236] The amount of stearic acid per 100 parts by mass of the rubber component is preferably 0.5 part by mass or more, more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.

[0237] The rubber composition may contain zinc oxide. As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., and the like.

[0238] The amount of zinc oxide per 100 parts by mass of the rubber component is preferably 0.5 part by mass or more, more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less.

[0239] The rubber composition may further contain other compounding agents (such as organic crosslinking agents) that are generally used in the tire industry in addition to the above components. The content of these compounding agents is preferably 0.1 to 200 parts by mass per 100 parts by mass of the rubber component.

[0240] The rubber composition can be produced, for example, by kneading the components using a rubber kneading device such as an open roll or a Banbury mixer, and then vulcanizing the mixture.

[0241] As for the kneading conditions, in the base kneading step in which additives other than the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 100 to 180°C, preferably 120 to 170°C. In the finish kneading step in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 120°C or lower, preferably 85 to 110°C. Furthermore, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is usually 140 to 190°C, preferably 150 to 185°C.

[0242] The heavy duty tire is produced by a conventional method using the above rubber composition. That is, the rubber composition is extruded in an unvulcanized state to match the shape of the tread, and molded together with other tire components in a tire building machine by a normal method to form an unvulcanized tire. The unvulcanized tire is then heated and pressurized in a vulcanizer to obtain a tire.

[0243] The heavy-duty tires include pneumatic tires and airless (solid) tires, with pneumatic tires being preferred.

[0244] [All-season tires] (Rubber component) The present invention relates to the following all-season tires (tires for all seasons) (1) to (3). A specific natural rubber derived from Russian dandelion, carbon black, and silica having a specific nitrogen adsorption specific surface area are used in combination in a specific blend, so that the overall performance of fuel economy, wear resistance, and wet grip performance is significantly (synergistically) improved.

[0245] (1) A natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The first all-season tire has a tread made of a rubber composition containing at least 100% silica and at least 100% silica in a predetermined blend ratio.

[0246] (2) A natural rubber derived from Russian dandelion having a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight-average molecular weight range of Mw 5 million to 50 million of 130 nm or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica in a predetermined blending ratio.

[0247] (3) A natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS, and a linear regression line having a slope of 0.25 or more in the weight average molecular weight range of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica in a predetermined blending ratio.

[0248] The reason (mechanism) why the overall performance of fuel economy, wear resistance, and wet grip performance is significantly (synergistically) improved is not necessarily clear, but is presumed to be as follows. The specific Russian dandelion-derived natural rubber of the present application has a higher Mw and contains a large amount of high molecular weight components compared to Hevea-derived natural rubber, which increases the breaking strength of the rubber. Also, the Russian dandelion-derived natural rubber has a lower degree of branching and contains a larger amount of linear polymers compared to Hevea-derived natural rubber, which increases the Rz of the polymer. Therefore, the high Rz of the polymer increases entanglement between polymers, and the increased probability of contact between the polymer and the filler increases interaction with the filler, which improves reinforcing properties, breaking properties, abrasion resistance, wet grip performance, etc.

[0249] Furthermore, the specific Russian dandelion-derived natural rubber of the present application has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, resulting in fewer free molecular ends and therefore fewer components that cause hysteresis loss, resulting in excellent low heat generation.

[0250] It is believed that by combining such natural rubber derived from Russian dandelion with carbon black and silica with a specific nitrogen adsorption specific surface area, the overall performance of fuel economy, abrasion resistance and wet grip performance will be significantly (synergistically) improved.

[0251] The natural rubber derived from Russian dandelion in the first to third all-season tires is the same as the natural rubber derived from Russian dandelion described above.

[0252] In the rubber composition, the content of the Russian dandelion-derived natural rubber is 1% by mass or more, preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, based on 100% by mass of the rubber component. The upper limit is not particularly limited, but is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less. By keeping the content within the above range, the overall performance of fuel economy, abrasion resistance, and wet grip performance is significantly improved.

[0253] The rubber composition may contain other rubber components together with the Russian dandelion-derived natural rubber. Examples of the other rubber components include those similar to those described above. The rubber components may be either unmodified or modified rubber. Among them, SBR and BR are preferred from the viewpoint of overall performance of fuel economy, abrasion resistance, and wet grip performance.

[0254] The SBR is not particularly limited, and for example, emulsion polymerized styrene butadiene rubber (E-SBR), solution polymerized styrene butadiene rubber (S-SBR), etc. can be used. These may be used alone or in combination of two or more kinds.

[0255] The styrene content of the SBR is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The styrene content is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less. By keeping it within the above range, good fuel economy, wet grip performance, abrasion resistance, etc. tend to be obtained. In this specification, the styrene content of SBR is H 1 - Calculated by NMR measurement.

[0256] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Co., Ltd., and the like can be used.

[0257] In the rubber composition, the content of SBR is preferably 10% by mass or more, more preferably 25% by mass or more, and even more preferably 35% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 80% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 55% by mass or less. By keeping the content within the above range, good fuel economy, wet grip performance, abrasion resistance, etc. tend to be obtained.

[0258] The BR is not particularly limited, and for example, the same BR as described above can be used.

[0259] In the rubber composition, the BR content is preferably 5% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less. By keeping the BR content within the above range, the overall performance of fuel economy, abrasion resistance, and wet grip performance is significantly improved.

[0260] (Carbon Black) The rubber composition contains carbon black. As the carbon black, the same carbon black as described above can be used.

[0261] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 50 m 2 / g or more, more preferably 70m 2 / g or more, more preferably 85m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200m 2 By making the N2SA of the carbon black equal to or higher than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or lower than the upper limit, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0262] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 50 ml / 100 g or more, more preferably 100 ml / 100 g or more, and even more preferably 110 ml / 100 g or more. The DBP is preferably 250 ml / 100 g or less, more preferably 200 ml / 100 g or less, and even more preferably 180 ml / 100 g or less. By setting it to the lower limit or more, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility is obtained, and excellent fuel efficiency tends to be obtained.

[0263] The aforementioned high-structure carbon black can also be suitably used as the carbon black. The suitable ranges of COAN, N2SA, volatile matter content at 900°C, volatile matter content at 1500°C, and pH of the high-structure carbon black are also the same.

[0264] In the rubber composition, the carbon black content is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. By making the content equal to or more than the lower limit, good abrasion resistance, wet grip performance, etc. tend to be obtained. By making the content equal to or less than the upper limit, good fuel economy tends to be obtained.

[0265] (silica) The rubber composition has a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica. As the silica, the same silica as described above can be used.

[0266] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 80m 2 / g or more, more preferably 100m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0267] As the silica, the above-mentioned finely divided silica can also be preferably used. The suitable N2SA range of the finely divided silica is also the same.

[0268] In the rubber composition, the content of silica (total amount of various silicas) is 10 parts by mass or more, preferably 40 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 60 parts by mass or more, per 100 parts by mass of the rubber component. In addition, good physical properties can be obtained even when the content of the silica is 120 parts by mass or more. The upper limit is preferably 250 parts by mass or less, more preferably 200 parts by mass or less, and even more preferably 180 parts by mass or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel efficiency tend to be obtained.

[0269] In the rubber composition, the total content of carbon black and silica is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 85 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 300 parts by mass or less, more preferably 250 parts by mass or less, and even more preferably 200 parts by mass or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0270] (Silane coupling agent) When the rubber composition contains silica, it is preferable to contain a silane coupling agent together with the silica. As the silane coupling agent, the same silane coupling agent as described above can be used. In addition, the mercapto-based silane coupling agent described above can also be suitably used.

[0271] When the rubber composition contains a silane coupling agent, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of silica. The content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By making the content equal to or more than the lower limit, the effect of improving dispersibility tends to be sufficiently obtained. By making the content equal to or less than the upper limit, the coupling effect tends to be sufficient, and good reinforcement tends to be obtained.

[0272] (Liquid plasticizer) The rubber composition may contain a liquid plasticizer (a plasticizer that is in a liquid state at room temperature (25° C.)). As the liquid plasticizer, the same liquid plasticizers as those described above can be used.

[0273] In the rubber composition, the content of the liquid plasticizer is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, good processability tends to be obtained. In addition, even if the content of the liquid plasticizer is blended with 50 parts by mass or more, good physical properties are obtained. The upper limit is preferably 120 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 90 parts by mass or less. By making it equal to or less than the upper limit, good abrasion resistance, wet grip performance, etc. tend to be obtained. The content of the liquid plasticizer includes the amount of oil (extending oil) contained in the rubber (oil-extended rubber). In addition, the content of the oil is also preferably in the same range.

[0274] (Solid Resin) The rubber composition may contain a solid resin (a polymer that is in a solid state at room temperature (25° C.)). As the solid resin, the same solid resin as described above can be used.

[0275] In the rubber composition, the content of the solid resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. When the content is within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0276] (Farnesene resin) The rubber composition preferably contains a farnesene-based resin. The farnesene-based resin may be the same as the farnesene-based resin described above. The preferred ranges of Tg, Mw, melt viscosity, farnesene content, and total content of farnesene and vinyl monomer are also the same.

[0277] In the rubber composition, the content of the farnesene resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. When the content is 1 part by mass or more, the performance improvement effect obtained by compounding the farnesene resin tends to be sufficiently obtained. In addition, the content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 20 parts by mass or less. When the content is 50 parts by mass or less, good fuel economy, wear resistance, wet grip performance, etc. tend to be obtained.

[0278] (Tetrazine compounds) The rubber composition may contain a tetrazine-based compound represented by the general formula (1). As the tetrazine-based compound, the same compounds as those described above can be used.

[0279] In the rubber composition, the content of the tetrazine-based compound (total amount of the tetrazine-based compound) is preferably 0.2 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, good overall performance of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0280] (fine particle zinc carrier) The rubber composition may be blended with a particulate zinc carrier in which zinc oxide fine particles or basic zinc carbonate fine particles are supported on the surface of silicate particles. As the particulate zinc carrier, the same ones as those described above can be used.

[0281] In the rubber composition, the content of the zinc microparticle carrier is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.6 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 2.0 parts by mass or less, more preferably 1.8 parts by mass or less, and even more preferably 1.6 parts by mass or less. By keeping the content within the above range, good overall performance of fuel economy, wear resistance, and wet grip performance tends to be obtained.

[0282] (Amide compounds) The rubber composition preferably contains an amide compound. As the amide compound, the same amide compounds as those described above can be used.

[0283] In the rubber composition, the content of the amide compound per 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0284] (sulfur) The rubber composition preferably contains sulfur. As the sulfur, the same sulfur as described above can be used.

[0285] In the rubber composition, the content of sulfur is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, and even more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0286] (Vulcanization accelerator) The rubber composition preferably contains a vulcanization accelerator. As the vulcanization accelerator, the same vulcanization accelerators as those described above can be used, among which sulfenamide-based vulcanization accelerators and guanidine-based vulcanization accelerators are preferred.

[0287] In the rubber composition, the content of the vulcanization accelerator is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, and even more preferably 2.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 5.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance can be obtained.

[0288] (Other ingredients) The rubber composition may further contain the above-mentioned wax, antioxidant, stearic acid, zinc oxide, and other compounding agents (organic crosslinking agent, etc.).

[0289] The rubber composition can be produced by the same method as for the above-mentioned rubber composition. The all-season tire can be manufactured in the same manner as the tire described above.

[0290] The all-season tires include pneumatic tires and airless (solid) tires, with pneumatic tires being preferred.

[0291] [Summer tires] (Rubber component) The present invention relates to the following summer tires (tires for summer use) (1) to (3). A specific Russian dandelion-derived natural rubber, a styrene-butadiene rubber with a specific styrene content, carbon black, and silica with a specific nitrogen adsorption specific surface area are used in combination in a specific blend, so that the overall performance of fuel economy, abrasion resistance, and wet grip performance is significantly (synergistically) improved.

[0292] (1) A mixture of Russian dandelion-derived natural rubber having a weight-average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, styrene-butadiene rubber with a styrene content of 10% by mass or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The first summer tire has a tread made of a rubber composition containing at least 1000 μm / g of silica in a predetermined blend ratio.

[0293] (2) A natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight average molecular weight range of Mw 5 million to 50 million of 130 nm or more, a styrene butadiene rubber having a styrene content of 10 mass% or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica in a predetermined blending ratio.

[0294] (3) A natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line having a weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm of the weight average molecular weight Mw versus the common logarithm of the radius of gyration Rz of the polymer (logRz) with a slope of 0.25 or more; a styrene butadiene rubber having a styrene content of 10% by mass or more; carbon black; and a nitrogen adsorption specific surface area of ​​40 m. 2 / g or more of silica in a predetermined blending ratio.

[0295] The reason (mechanism) why the overall performance of fuel economy, wear resistance, and wet grip performance is significantly (synergistically) improved is not necessarily clear, but is presumed to be as follows. The specific Russian dandelion-derived natural rubber of the present application has a higher Mw and contains a large amount of high molecular weight components compared to Hevea-derived natural rubber, which increases the breaking strength of the rubber. Also, the Russian dandelion-derived natural rubber has a lower degree of branching and contains a larger amount of linear polymers compared to Hevea-derived natural rubber, which increases the Rz of the polymer. Therefore, the high Rz of the polymer increases entanglement between polymers, and the increased probability of contact between the polymer and the filler increases interaction with the filler, which improves reinforcing properties, breaking properties, abrasion resistance, wet grip performance, etc.

[0296] Furthermore, the specific Russian dandelion-derived natural rubber of the present application has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, resulting in fewer free molecular ends and therefore fewer components that cause hysteresis loss, resulting in excellent low heat generation.

[0297] It is believed that by combining such natural rubber derived from Russian dandelion, styrene-butadiene rubber with a specific styrene content, carbon black, and silica with a specific nitrogen adsorption specific surface area, the overall performance of fuel economy, abrasion resistance, and wet grip performance will be significantly (synergistically) improved.

[0298] The natural rubber derived from Russian dandelion in the first to third summer tires is the same as the natural rubber derived from Russian dandelion described above.

[0299] In the rubber composition, the content of the Russian dandelion-derived natural rubber is 0.1% by mass or more, preferably 1.0% by mass or more, and more preferably 3.0% by mass or more, based on 100% by mass of the rubber component. The upper limit is 10.0% by mass or less, preferably 8.0% by mass or less, and more preferably 7.0% by mass or less. By keeping the content within the above range, the overall performance of fuel economy, abrasion resistance, and wet grip performance is significantly improved.

[0300] The rubber composition contains a styrene-butadiene rubber having a specific styrene content (high styrene SBR) as a rubber component. These may be used alone or in combination of two or more kinds.

[0301] The styrene content of the high styrene SBR is 10% by mass or more, preferably 20% by mass or more, and more preferably 25% by mass or more. By making it equal to or more than the lower limit, good wet grip performance and the like tend to be obtained. Moreover, the upper limit of the styrene content is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less. By making it equal to or less than the upper limit, good fuel economy tends to be obtained. In this specification, the styrene content of SBR is H 1 - Calculated by NMR measurement.

[0302] The vinyl content of the high styrene SBR (the vinyl content in the butadiene component of the SBR) is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more. The vinyl content is preferably 65% ​​by mass or less, more preferably 60% by mass or less. By keeping it within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0303] The weight average molecular weight (Mw) of the high styrene SBR is preferably 400,000 or more, more preferably 700,000 or more, and even more preferably 800,000 or more. By making it equal to or higher than the lower limit, good abrasion resistance and the like tend to be obtained. The Mw is preferably 1.8 million or less, more preferably 1.6 million or less, and even more preferably 1.4 million or less. By making it equal to or lower than the upper limit, good processability tends to be obtained.

[0304] The high styrene SBR is not particularly limited, and for example, emulsion polymerized styrene butadiene rubber (E-SBR), solution polymerized styrene butadiene rubber (S-SBR), etc. can be used. The SBR may be either non-oil extended SBR or oil extended SBR. In addition, the SBR may be either non-modified SBR or modified SBR.

[0305] Oil-extended SBR is SBR that has been oil-extended using an extender oil. Examples of extender oils used for oil-extending SBR include naphthenic, paraffinic, and aromatic oil-extending oils. Examples of the oil-extending method include a method in which an extender oil is added after polymerization is completed, and the solvent is removed and the oil is dried by a conventionally known method. The amount of extender oil used is preferably 5 to 70 parts by mass, more preferably 10 to 50 parts by mass, and even more preferably 15 to 45 parts by mass, based on 100 parts by mass of SBR (rubber solid content).

[0306] The modified SBR may be any SBR having a functional group that interacts with a filler such as silica, and examples thereof include terminal-modified SBR in which at least one end of SBR has been modified with a compound (modifying agent) having the above-mentioned functional group (terminal-modified SBR having the above-mentioned functional group at the end), main-chain-modified SBR having the above-mentioned functional group in the main chain, main-chain terminal-modified SBR having the above-mentioned functional group in the main chain and at least one end (for example, main-chain terminal-modified SBR having the above-mentioned functional group in the main chain and at least one end modified with the above-mentioned modifier), and terminal-modified SBR modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or epoxy group introduced therein.

[0307] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), and an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms) are preferred.

[0308] As the modified SBR, in particular, SBR modified with a compound (modifier) ​​represented by the following formula is preferred. [ka] (In the formula, R 1 , R 2 and R 3 R may be the same or different and represents an alkyl group, an alkoxy group, a silyloxy group, an acetal group, a carboxyl group (-COOH), a mercapto group (-SH), or a derivative thereof. 4 and R 5 R may be the same or different and represents a hydrogen atom or an alkyl group. 4 and R 5 may be bonded to form a ring structure together with the nitrogen atom, and n represents an integer.

[0309] As the modified SBR modified with a compound (modifier) ​​represented by the above formula, SBR in which the polymerization terminals (active terminals) of solution-polymerized styrene-butadiene rubber (S-SBR) have been modified with a compound represented by the above formula (such as the modified SBR described in JP-A-2010-111753).

[0310] R 1 , R 2 and R3 R is preferably an alkoxy group (preferably an alkoxy group having 1 to 8 carbon atoms, more preferably an alkoxy group having 1 to 4 carbon atoms). 4 and R 5 is preferably an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms). n is preferably 1 to 5, more preferably 2 to 4, and further preferably 3. In addition, R 4 and R 5 When the nitrogen atom and the nitrogen atom are bonded to each other to form a ring structure, the ring is preferably a 4- to 8-membered ring. The alkoxy group also includes a cycloalkoxy group (such as a cyclohexyloxy group) and an aryloxy group (such as a phenoxy group and a benzyloxy group).

[0311] Specific examples of the above-mentioned modifying agent include 2-dimethylaminoethyl trimethoxysilane, 3-dimethylaminopropyl trimethoxysilane, 2-dimethylaminoethyl triethoxysilane, 3-dimethylaminopropyl triethoxysilane, 2-diethylaminoethyl trimethoxysilane, 3-diethylaminopropyl trimethoxysilane, 2-diethylaminoethyl triethoxysilane, 3-diethylaminopropyl triethoxysilane, etc. Among them, 3-dimethylaminopropyl trimethoxysilane, 3-dimethylaminopropyl triethoxysilane, and 3-diethylaminopropyl trimethoxysilane are preferred. These may be used alone or in combination of two or more.

[0312] The modified SBR may be modified with the following compounds (modifiers): Examples of the modifiers include polyglycidyl ethers of polyhydric alcohols such as ethylene glycol diglycidyl ether, glycerin triglycidyl ether, trimethylolethane triglycidyl ether, and trimethylolpropane triglycidyl ether; polyglycidyl ethers of aromatic compounds having two or more phenol groups such as diglycidylated bisphenol A; polyepoxy compounds such as 1,4-diglycidylbenzene, 1,3,5-triglycidylbenzene, and polyepoxidized liquid polybutadiene; and 4,4'- Epoxy group-containing tertiary amines such as diglycidyl-diphenylmethylamine and 4,4'-diglycidyl-dibenzylmethylamine; diglycidyl amino compounds such as diglycidyl aniline, N,N'-diglycidyl-4-glycidyloxyaniline, diglycidyl orthotoluidine, tetraglycidyl meta-xylylenediamine, tetraglycidyl aminodiphenylmethane, tetraglycidyl-p-phenylenediamine, diglycidyl aminomethylcyclohexane, and tetraglycidyl-1,3-bisaminomethylcyclohexane;

[0313] Amino group-containing acid chlorides such as bis-(1-methylpropyl)carbamic acid chloride, 4-morpholinecarbonyl chloride, 1-pyrrolidinecarbonyl chloride, N,N-dimethylcarbamic acid chloride, and N,N-diethylcarbamic acid chloride; epoxy group-containing silane compounds such as 1,3-bis-(glycidyloxypropyl)-tetramethyldisiloxane and (3-glycidyloxypropyl)-pentamethyldisiloxane;

[0314] Sulfide group-containing silane compounds such as (trimethylsilyl)[3-(trimethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(triethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(tripropoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(tributoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(methyldimethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(methyldiethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(methyldipropoxysilyl)propyl]sulfide, and (trimethylsilyl)[3-(methyldibutoxysilyl)propyl]sulfide;

[0315] N-substituted aziridine compounds such as ethyleneimine and propyleneimine; alkoxysilanes such as methyltriethoxysilane; (thio)benzophenone compounds having amino groups and / or substituted amino groups such as 4-N,N-dimethylaminobenzophenone, 4-N,N-di-t-butylaminobenzophenone, 4-N,N-diphenylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(diphenylamino)benzophenone, and N,N,N',N'-bis-(tetraethylamino)benzophenone; 4-N,N-dimethylaminobenzaldehyde, 4-N,N-diphenylaminobenzaldehyde, 4-N benzaldehyde compounds having an amino group and / or a substituted amino group, such as N-divinylaminobenzaldehyde; N-substituted pyrrolidones, such as N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, N-phenyl-2-pyrrolidone, Nt-butyl-2-pyrrolidone, and N-methyl-5-methyl-2-pyrrolidone; N-substituted piperidones, such as N-methyl-2-piperidone, N-vinyl-2-piperidone, and N-phenyl-2-piperidone; N-substituted lactams, such as N-methyl-ε-caprolactam, N-phenyl-ε-caprolactam, N-methyl-ω-laurylolactam, N-vinyl-ω-laurylolactam, N-methyl-β-propiolactam, and N-phenyl-β-propiolactam; and

[0316] Examples of the copolymer include N,N-bis-(2,3-epoxypropoxy)-aniline, 4,4-methylene-bis-(N,N-glycidylaniline), tris-(2,3-epoxypropyl)-1,3,5-triazine-2,4,6-triones, N,N-diethylacetamide, N-methylmaleimide, N,N-diethylurea, 1,3-dimethylethyleneurea, 1,3-divinylethyleneurea, 1,3-diethyl-2-imidazolidinone, 1-methyl-3-ethyl-2-imidazolidinone, 4-N,N-dimethylaminoacetophene, 4-N,N-diethylaminoacetophenone, 1,3-bis(diphenylamino)-2-propanone, and 1,7-bis(methylethylamino)-4-heptanone. Among these, modified SBR modified with alkoxysilane is preferred. The modification with the above compound (modifying agent) can be carried out by a known method.

[0317] As the high styrene SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Co., Ltd., and the like can be used.

[0318] In the rubber composition, the content of the high styrene SBR is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less. By keeping the content within the above range, good fuel economy, wet grip performance, abrasion resistance, etc. tend to be obtained.

[0319] The rubber composition may contain other rubber components together with the Russian dandelion-derived natural rubber and high styrene SBR. Examples of the other rubber components include those similar to those described above. The rubber components may be either unmodified or modified rubber. Among them, BR is preferred from the viewpoint of overall performance of fuel economy, abrasion resistance, and wet grip performance.

[0320] The BR is not particularly limited, and for example, the same BR as described above can be used.

[0321] In the rubber composition, the BR content is preferably 1% by mass or more, more preferably 7% by mass or more, and even more preferably 10% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less. By keeping the BR content within the above range, the overall performance of fuel economy, abrasion resistance, and wet grip performance is significantly improved.

[0322] (Carbon Black) The rubber composition contains carbon black. As the carbon black, the same carbon black as described above can be used.

[0323] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 50 m 2 / g or more, more preferably 70m 2 / g or more, more preferably 85m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200m 2 By making the N2SA of the carbon black equal to or higher than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or lower than the upper limit, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0324] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 50 ml / 100 g or more, more preferably 100 ml / 100 g or more, and even more preferably 110 ml / 100 g or more. The DBP is preferably 250 ml / 100 g or less, more preferably 200 ml / 100 g or less, and even more preferably 180 ml / 100 g or less. By setting it to the lower limit or more, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility is obtained, and excellent fuel efficiency tends to be obtained.

[0325] The aforementioned high-structure carbon black can also be suitably used as the carbon black. The suitable ranges of COAN, N2SA, volatile matter content at 900°C, volatile matter content at 1500°C, and pH of the high-structure carbon black are also the same.

[0326] In the rubber composition, the carbon black content is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. By making the content equal to or more than the lower limit, good abrasion resistance, wet grip performance, etc. tend to be obtained. By making the content equal to or less than the upper limit, good fuel economy tends to be obtained.

[0327] (silica) The rubber composition has a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica. As the silica, the same silica as described above can be used.

[0328] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 80m 2 / g or more, more preferably 100m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0329] As the silica, the above-mentioned finely divided silica can also be preferably used. The suitable N2SA range of the finely divided silica is also the same.

[0330] In the rubber composition, the content of silica (total amount of various silicas) is 10 parts by mass or more, preferably 40 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 60 parts by mass or more, per 100 parts by mass of the rubber component. In addition, good physical properties can be obtained even when the content of the silica is 120 parts by mass or more. The upper limit is preferably 250 parts by mass or less, more preferably 200 parts by mass or less, and even more preferably 180 parts by mass or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel efficiency tend to be obtained.

[0331] In the rubber composition, the total content of carbon black and silica is preferably 40 parts by mass or more, more preferably 60 parts by mass or more, and even more preferably 70 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 300 parts by mass or less, more preferably 250 parts by mass or less, and even more preferably 200 parts by mass or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0332] (Silane coupling agent) When the rubber composition contains silica, it is preferable to contain a silane coupling agent together with the silica. As the silane coupling agent, the same silane coupling agent as described above can be used. In addition, the mercapto-based silane coupling agent described above can also be suitably used.

[0333] When the rubber composition contains a silane coupling agent, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of silica. The content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By making the content equal to or more than the lower limit, the effect of improving dispersibility tends to be sufficiently obtained. By making the content equal to or less than the upper limit, the coupling effect tends to be sufficient, and good reinforcement tends to be obtained.

[0334] (Liquid plasticizer) The rubber composition may contain a liquid plasticizer (a plasticizer that is in a liquid state at room temperature (25° C.)). As the liquid plasticizer, the same liquid plasticizers as those described above can be used.

[0335] In the rubber composition, the content of the liquid plasticizer is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, good processability tends to be obtained. In addition, even if the content of the liquid plasticizer is blended with 50 parts by mass or more, good physical properties are obtained. The upper limit is preferably 150 parts by mass or less, more preferably 130 parts by mass or less, and even more preferably 110 parts by mass or less. By making it equal to or less than the upper limit, good abrasion resistance, wet grip performance, etc. tend to be obtained. The content of the liquid plasticizer also includes the amount of oil (extending oil) contained in the rubber (oil-extended rubber). In addition, the content of the oil is also preferably in the same range.

[0336] (Solid Resin) The rubber composition may contain a solid resin (a polymer that is in a solid state at room temperature (25° C.)). As the solid resin, the same solid resin as described above can be used.

[0337] In the rubber composition, the content of the solid resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. When the content is within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0338] (Farnesene resin) The rubber composition preferably contains a farnesene-based resin. The farnesene-based resin may be the same as the farnesene-based resin described above. The preferred ranges of Tg, Mw, melt viscosity, farnesene content, and total content of farnesene and vinyl monomer are also the same.

[0339] In the rubber composition, the content of the farnesene resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. When the content is 1 part by mass or more, the performance improvement effect obtained by compounding the farnesene resin tends to be sufficiently obtained. In addition, the content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 20 parts by mass or less. When the content is 50 parts by mass or less, good fuel economy, wear resistance, wet grip performance, etc. tend to be obtained.

[0340] (Tetrazine compounds) The rubber composition may contain a tetrazine-based compound represented by the general formula (1). As the tetrazine-based compound, the same compounds as those described above can be used.

[0341] In the rubber composition, the content of the tetrazine-based compound (total amount of the tetrazine-based compound) is preferably 0.2 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, good overall performance of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0342] (fine particle zinc carrier) The rubber composition may be blended with a particulate zinc carrier in which zinc oxide fine particles or basic zinc carbonate fine particles are supported on the surface of silicate particles. As the particulate zinc carrier, the same ones as those described above can be used.

[0343] In the rubber composition, the content of the zinc microparticle carrier is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.6 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 2.0 parts by mass or less, more preferably 1.8 parts by mass or less, and even more preferably 1.6 parts by mass or less. By keeping the content within the above range, good overall performance of fuel economy, wear resistance, and wet grip performance tends to be obtained.

[0344] (Amide compounds) The rubber composition preferably contains an amide compound. As the amide compound, the same amide compounds as those described above can be used.

[0345] In the rubber composition, the content of the amide compound per 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0346] (sulfur) The rubber composition preferably contains sulfur. As the sulfur, the same sulfur as described above can be used.

[0347] In the rubber composition, the content of sulfur is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, and even more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance tends to be obtained.

[0348] (Vulcanization accelerator) The rubber composition preferably contains a vulcanization accelerator. As the vulcanization accelerator, the same vulcanization accelerators as those described above can be used, among which sulfenamide-based vulcanization accelerators and guanidine-based vulcanization accelerators are preferred.

[0349] In the rubber composition, the content of the vulcanization accelerator is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, and even more preferably 2.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 5.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy, abrasion resistance, and wet grip performance can be obtained.

[0350] (Other ingredients) The rubber composition may further contain the above-mentioned wax, antioxidant, stearic acid, zinc oxide, and other compounding agents (organic crosslinking agent, etc.).

[0351] The rubber composition can be produced by the same method as for the above-mentioned rubber composition. The summer tire can be manufactured in the same manner as the tire described above.

[0352] The summer tires include pneumatic tires and airless (solid) tires, with pneumatic tires being preferred.

[0353] [Studless tires] (Rubber component) The present invention relates to studless tires (winter tires) according to the following (1) to (3). A specific Russian dandelion-derived natural rubber, a butadiene rubber having a specific cis-1,4-bond amount, carbon black, and silica having a specific nitrogen adsorption specific surface area are used in combination in a specific blend, which significantly (synergistically) improves the overall performance of fuel economy, abrasion resistance, and performance on snow and ice.

[0354] (1) A mixture of Russian dandelion-derived natural rubber having a weight-average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, butadiene rubber with a cis-1,4-bond content of 94.0 mass% or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 The first studless tire has a tread made using a rubber composition containing at least 100% silica and at least 100% silica in a predetermined blend ratio.

[0355] (2) A natural rubber derived from Russian dandelion having a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight-average molecular weight range of Mw 5 million to 50 million of 130 nm or more, a butadiene rubber having a cis-1,4-bond content of 94.0 mass% or more, carbon black, and a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica in a predetermined blending ratio.

[0356] (3) A natural rubber derived from Russian dandelion having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line having a weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer, the slope of which is 0.25 or more; butadiene rubber having a cis-1,4-bond content of 94.0% by mass or more; carbon black; and a nitrogen adsorption specific surface area of ​​40 m. 2 / g or more of silica in a predetermined blending ratio.

[0357] The reason (mechanism) why the overall performance of excellent fuel economy, wear resistance, and performance on snow and ice is significantly (synergistically) improved is not necessarily clear, but is presumed to be as follows. The specific Russian dandelion-derived natural rubber of the present application has a higher Mw and contains a larger amount of high molecular weight components than Hevea-derived natural rubber, which increases the breaking strength of the rubber. Furthermore, the Russian dandelion-derived natural rubber has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, which increases the Rz of the polymer. Therefore, the higher Rz of the polymer increases entanglement between polymers, and the higher probability of contact between the polymer and the filler increases interaction with the filler, improving reinforcing properties and improving breaking properties, abrasion resistance, performance on snow and ice, etc.

[0358] Furthermore, the specific Russian dandelion-derived natural rubber of the present application has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, resulting in fewer free molecular ends and therefore fewer components that cause hysteresis loss, resulting in excellent low heat generation.

[0359] It is believed that by combining such natural rubber derived from Russian dandelion, butadiene rubber with a specific cis-1,4-bond amount, carbon black, and silica with a specific nitrogen adsorption specific surface area, the overall performance of fuel economy, abrasion resistance, and performance on snow and ice will be significantly (synergistically) improved.

[0360] The natural rubber derived from the Russian dandelion in the first to third studless tires is the same as the natural rubber derived from the Russian dandelion described above.

[0361] In the rubber composition, the content of the Russian dandelion-derived natural rubber is 1% by mass or more, preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. By keeping the content within the above range, the overall performance of fuel economy, abrasion resistance, and performance on snow and ice is significantly improved.

[0362] The rubber composition contains a butadiene rubber having a specific cis-1,4-bond content (high cis BR) as a rubber component. These may be used alone or in combination of two or more kinds.

[0363] The high cis BR has a cis-1,4-bond content of 94.0% by mass or more, preferably 95.0% by mass or more, more preferably 97.0% by mass or more, and even more preferably 98.0% by mass or more. By keeping the content within the above range, abrasion resistance and the like tend to be improved.

[0364] The high cis BR may be a general-purpose high cis BR having a high cis content, a BR synthesized using a rare earth catalyst (rare earth BR), etc. In addition, the above-mentioned modified BR (modified conjugated diene polymer) may also be suitably used as the high cis BR. The high cis BR may be either unmodified or modified.

[0365] In the rubber composition, the content of high cis BR is 20% by mass or more, preferably 25% by mass or more, more preferably 30% by mass or more, based on 100% by mass of the rubber component. The upper limit is 64% by mass or less, preferably 55% by mass or less, more preferably 50% by mass or less. By keeping the content within the above range, the overall performance of fuel economy, abrasion resistance, and performance on snow and ice is significantly improved.

[0366] (Carbon Black) The rubber composition contains carbon black. As the carbon black, the same carbon black as described above can be used.

[0367] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 50 m 2 / g or more, more preferably 70m 2 / g or more, more preferably 85m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200m 2By setting the N2SA of carbon black at or above the lower limit, excellent abrasion resistance and performance on snow and ice tend to be obtained. By setting it at or below the upper limit, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0368] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 50 ml / 100 g or more, more preferably 100 ml / 100 g or more, and even more preferably 110 ml / 100 g or more. The DBP is preferably 250 ml / 100 g or less, more preferably 200 ml / 100 g or less, and even more preferably 180 ml / 100 g or less. By setting it to the lower limit or more, excellent abrasion resistance, performance on snow and ice, etc. tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility and excellent fuel efficiency tend to be obtained.

[0369] The aforementioned high-structure carbon black can also be suitably used as the carbon black. The suitable ranges of COAN, N2SA, volatile matter content at 900°C, volatile matter content at 1500°C, and pH of the high-structure carbon black are also the same.

[0370] In the rubber composition, the carbon black content is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. By making the content equal to or more than the lower limit, good abrasion resistance, performance on snow and ice, etc. tend to be obtained. By making the content equal to or less than the upper limit, good fuel economy tends to be obtained.

[0371] (silica) The rubber composition has a nitrogen adsorption specific surface area of ​​40 m 2 / g or more of silica. As the silica, the same silica as described above can be used.

[0372] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 50 m 2 / g or more, more preferably 80m 2 / g or more, more preferably 100m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less. By making it equal to or more than the lower limit, excellent abrasion resistance, wet grip performance, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0373] As the silica, the above-mentioned finely divided silica can also be preferably used. The suitable N2SA range of the finely divided silica is also the same.

[0374] In the rubber composition, the content of silica (total amount of various silicas) is 5 parts by mass or more, preferably 40 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 60 parts by mass or more, per 100 parts by mass of the rubber component. In addition, good physical properties can be obtained even when the content of the silica is 120 parts by mass or more. The upper limit is preferably 250 parts by mass or less, more preferably 200 parts by mass or less, and even more preferably 180 parts by mass or less. By making it equal to or more than the lower limit, excellent abrasion resistance, performance on snow and ice, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0375] In the rubber composition, the total content of carbon black and silica is preferably 40 parts by mass or more, more preferably 60 parts by mass or more, and even more preferably 70 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 300 parts by mass or less, more preferably 250 parts by mass or less, and even more preferably 200 parts by mass or less. By making the content equal to or more than the lower limit, excellent abrasion resistance, performance on snow and ice, etc. tend to be obtained. By making the content equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0376] (Silane coupling agent) When the rubber composition contains silica, it is preferable to contain a silane coupling agent together with the silica. As the silane coupling agent, the same silane coupling agent as described above can be used. In addition, the mercapto-based silane coupling agent described above can also be suitably used.

[0377] When the rubber composition contains a silane coupling agent, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of silica. The content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By making the content equal to or more than the lower limit, the effect of improving dispersibility tends to be sufficiently obtained. By making the content equal to or less than the upper limit, the coupling effect tends to be sufficient, and good reinforcement tends to be obtained.

[0378] (Liquid plasticizer) The rubber composition may contain a liquid plasticizer (a plasticizer that is in a liquid state at room temperature (25° C.)). As the liquid plasticizer, the same liquid plasticizers as those described above can be used.

[0379] In the rubber composition, the content of the liquid plasticizer is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, good processability tends to be obtained. In addition, even if the content of the liquid plasticizer is blended with 50 parts by mass or more, good physical properties are obtained. The upper limit is preferably 150 parts by mass or less, more preferably 120 parts by mass or less, and even more preferably 100 parts by mass or less. By making it equal to or less than the upper limit, good abrasion resistance, performance on snow and ice, etc. tend to be obtained. The content of the liquid plasticizer includes the amount of oil (extending oil) contained in the rubber (oil-extended rubber). In addition, the content of the oil is also preferably in the same range.

[0380] (Solid Resin) The rubber composition may contain a solid resin (a polymer that is in a solid state at room temperature (25° C.)). As the solid resin, the same solid resin as described above can be used.

[0381] In the rubber composition, the content of the solid resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. When the content is within the above range, good overall performance in terms of fuel economy, abrasion resistance, and performance on snow and ice tends to be obtained.

[0382] (Farnesene resin) The rubber composition preferably contains a farnesene-based resin. The farnesene-based resin may be the same as the farnesene-based resin described above. The preferred ranges of Tg, Mw, melt viscosity, farnesene content, and total content of farnesene and vinyl monomer are also the same.

[0383] In the rubber composition, the content of the farnesene resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. When the content is 1 part by mass or more, the performance improvement effect obtained by compounding the farnesene resin tends to be sufficiently obtained. In addition, the content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 20 parts by mass or less. When the content is 50 parts by mass or less, good fuel economy, wear resistance, performance on snow and ice, etc. tend to be obtained.

[0384] (Tetrazine compounds) The rubber composition may contain a tetrazine-based compound represented by the general formula (1). As the tetrazine-based compound, the same compounds as those described above can be used.

[0385] In the rubber composition, the content of the tetrazine-based compounds (total amount of the tetrazine-based compounds) is preferably 0.2 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, wear resistance, and performance on snow and ice tends to be obtained.

[0386] (fine particle zinc carrier) The rubber composition may be blended with a particulate zinc carrier in which zinc oxide fine particles or basic zinc carbonate fine particles are supported on the surface of silicate particles. As the particulate zinc carrier, the same ones as those described above can be used.

[0387] In the rubber composition, the content of the zinc microparticle carrier is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.6 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 2.0 parts by mass or less, more preferably 1.8 parts by mass or less, and even more preferably 1.6 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, wear resistance, and performance on snow and ice tends to be obtained.

[0388] (Amide compounds) The rubber composition preferably contains an amide compound. As the amide compound, the same amide compounds as those described above can be used.

[0389] In the rubber composition, the content of the amide compound per 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, abrasion resistance, and performance on snow and ice tends to be obtained.

[0390] (sulfur) The rubber composition preferably contains sulfur. As the sulfur, the same sulfur as described above can be used.

[0391] In the rubber composition, the sulfur content is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, and even more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy, abrasion resistance, and performance on snow and ice can be obtained.

[0392] (Vulcanization accelerator) The rubber composition preferably contains a vulcanization accelerator. As the vulcanization accelerator, the same vulcanization accelerators as those described above can be used, among which sulfenamide-based vulcanization accelerators and guanidine-based vulcanization accelerators are preferred.

[0393] In the rubber composition, the content of the vulcanization accelerator is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, and even more preferably 2.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 5.0 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy, abrasion resistance, and performance on snow and ice tends to be obtained.

[0394] (Other ingredients) The rubber composition may further contain the above-mentioned wax, antioxidant, stearic acid, zinc oxide, and other compounding agents (organic crosslinking agent, etc.).

[0395] The rubber composition can be produced by the same method as for the above-mentioned rubber composition. The studless tire can be manufactured in the same manner as the above-mentioned tire.

[0396] Examples of the studless tires include pneumatic tires and airless (solid) tires, with pneumatic tires being preferred.

[0397] [Base tread] (Rubber component) The present invention is a tire having a base tread as described below in (1) to (3). Since a specific natural rubber derived from Russian dandelion, carbon black, and silica are used in combination in a predetermined ratio, the overall performance of fuel economy and fracture resistance is significantly (synergistically) improved.

[0398] (1) A first tire having a base tread made using a rubber composition containing, in a predetermined blend, natural rubber derived from Russian dandelion, having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, carbon black, and silica.

[0399] (2) A second tire having a base tread made using a rubber composition containing, in a predetermined blend, natural rubber derived from Russian dandelion, having a weight-average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight-average molecular weight range of Mw 5 million to 50 million of 130 nm or more, carbon black, and silica.

[0400] (3) A third tire having a base tread made using a rubber composition containing, in a predetermined blend, natural rubber derived from Russian dandelion, carbon black, and silica, the weight average molecular weight Mw of which is 5 million or more as measured by FFF-MALS, and the slope of a linear regression line in a weight average molecular weight region of 5 million to 50 million in a plot of the common logarithm of the weight average molecular weight Mw (logMw) versus the common logarithm of the radius of gyration Rz of the polymer (logRz), is 0.25 or more.

[0401] The reason (mechanism) why the overall performance of excellent fuel economy and fracture resistance is significantly (synergistically) improved is not necessarily clear, but is presumed to be as follows. The specific Russian dandelion-derived natural rubber of the present application has a higher Mw and contains a larger amount of high molecular weight components than Hevea-derived natural rubber, which increases the breaking strength of the rubber. Furthermore, the Russian dandelion-derived natural rubber has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, which increases the Rz of the polymer. Therefore, the higher Rz of the polymer increases entanglement between polymers, and the higher probability of contact between the polymer and the filler increases interaction with the filler, improving reinforcing properties and breaking resistance.

[0402] Furthermore, the specific Russian dandelion-derived natural rubber of the present application has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, resulting in fewer free molecular ends and therefore fewer components that cause hysteresis loss, resulting in excellent low heat generation.

[0403] It is presumed that by combining such natural rubber derived from Russian dandelion with carbon black and silica in a specified blend, the overall performance of fuel economy and fracture resistance will be significantly (synergistically) improved.

[0404] The natural rubber derived from the Russian dandelion in the first to third tires is the same as the natural rubber derived from the Russian dandelion described above.

[0405] In the rubber composition, the content of the Russian dandelion-derived natural rubber is 1% by mass or more, preferably 50% by mass or more, and more preferably 60% by mass or more, based on 100% by mass of the rubber component. The upper limit is not particularly limited, but is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less. By keeping the content within the above range, the overall performance of fuel economy and fracture resistance is significantly improved.

[0406] The rubber composition may contain other rubber components together with the Russian dandelion-derived natural rubber. Examples of the other rubber components include those similar to those described above. The rubber components may be either unmodified or modified rubber. Among them, BR is preferred from the viewpoint of overall performance of fuel economy and fracture resistance.

[0407] The BR is not particularly limited, and for example, the same BR as described above can be used.

[0408] In the rubber composition, the BR content is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less. By keeping the BR content within the above range, the overall performance of fuel economy and fracture resistance is significantly improved.

[0409] (Carbon Black) The rubber composition contains carbon black. As the carbon black, the same carbon black as described above can be used.

[0410] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 50 m 2 / g or more, more preferably 70m 2 / g or more, more preferably 85m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200m 2 By setting the N2SA of carbon black to the lower limit or higher, excellent fracture resistance and other properties tend to be obtained. By setting it to the upper limit or lower, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0411] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 50 ml / 100 g or more, more preferably 100 ml / 100 g or more, and even more preferably 110 ml / 100 g or more. The DBP is preferably 250 ml / 100 g or less, more preferably 200 ml / 100 g or less, and even more preferably 180 ml / 100 g or less. By setting it to the lower limit or more, excellent fracture resistance and the like tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0412] The aforementioned high-structure carbon black can also be suitably used as the carbon black. The suitable ranges of COAN, N2SA, volatile matter content at 900°C, volatile matter content at 1500°C, and pH of the high-structure carbon black are also the same.

[0413] In the rubber composition, the carbon black content is preferably 5 parts by mass or more, more preferably 25 parts by mass or more, and even more preferably 35 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 100 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 55 parts by mass or less. By making the content equal to or more than the lower limit, good fracture resistance and the like tend to be obtained. By making the content equal to or less than the upper limit, good fuel economy tends to be obtained.

[0414] (silica) The rubber composition contains silica. As the silica, the same silica as described above can be used.

[0415] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 20 m 2 / g or more, more preferably 30m 2 / g or more, more preferably 40m 2 / g or more. In addition, the N2SA is preferably 300m 2 / g or less, more preferably 250m 2 / g or less. By making it equal to or more than the lower limit, excellent fracture resistance and the like tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0416] As the silica, the above-mentioned finely divided silica can also be preferably used. The suitable N2SA range of the finely divided silica is also the same.

[0417] In the rubber composition, the content of silica (total amount of various silicas) is 10 parts by mass or more, preferably 13 parts by mass or more, more preferably 15 parts by mass or more, per 100 parts by mass of the rubber component. In addition, good physical properties can be obtained even when the content of the silica is 120 parts by mass or more. The upper limit is preferably 250 parts by mass or less, more preferably 200 parts by mass or less, and even more preferably 180 parts by mass or less. By making it equal to or more than the lower limit, excellent fracture resistance performance and the like tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0418] In the rubber composition, the total content of carbon black and silica is preferably 40 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 55 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 300 parts by mass or less, more preferably 250 parts by mass or less, and even more preferably 220 parts by mass or less. By making the content equal to or more than the lower limit, excellent fracture resistance and the like tend to be obtained. By making the content equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0419] (Silane coupling agent) When the rubber composition contains silica, it is preferable to contain a silane coupling agent together with the silica. As the silane coupling agent, the same silane coupling agent as described above can be used. In addition, the mercapto-based silane coupling agent described above can also be suitably used.

[0420] When the rubber composition contains a silane coupling agent, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of silica. The content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By making the content equal to or more than the lower limit, the effect of improving dispersibility tends to be sufficiently obtained. By making the content equal to or less than the upper limit, the coupling effect tends to be sufficient, and good reinforcement tends to be obtained.

[0421] (Liquid plasticizer) The rubber composition may contain a liquid plasticizer (a plasticizer that is in a liquid state at room temperature (25° C.)). As the liquid plasticizer, the same liquid plasticizers as those described above can be used.

[0422] In the rubber composition, the content of the liquid plasticizer is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, good processability tends to be obtained. In addition, even if the content of the liquid plasticizer is blended with 50 parts by mass or more, good physical properties are obtained. The upper limit is preferably 120 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 90 parts by mass or less. By making it equal to or less than the upper limit, good fracture resistance performance tends to be obtained. The content of the liquid plasticizer includes the amount of oil (extending oil) contained in the rubber (oil-extended rubber). In addition, the content of the oil is also preferably in the same range.

[0423] (Solid Resin) The rubber composition may contain a solid resin (a polymer that is in a solid state at room temperature (25° C.)). As the solid resin, the same solid resin as described above can be used.

[0424] In the rubber composition, the content of the solid resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. When the content is within the above range, good overall performance in terms of fuel economy and fracture resistance tends to be obtained.

[0425] (Farnesene resin) The rubber composition preferably contains a farnesene-based resin. The farnesene-based resin may be the same as the farnesene-based resin described above. The preferred ranges of Tg, Mw, melt viscosity, farnesene content, and total content of farnesene and vinyl monomer are also the same.

[0426] In the rubber composition, the content of the farnesene resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. When the content is 1 part by mass or more, the performance improvement effect obtained by compounding the farnesene resin tends to be sufficiently obtained. In addition, the content is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 20 parts by mass or less. When the content is 50 parts by mass or less, good fuel economy, fracture resistance, etc. tend to be obtained.

[0427] (Tetrazine compounds) The rubber composition may contain a tetrazine-based compound represented by the general formula (1). As the tetrazine-based compound, the same compounds as those described above can be used.

[0428] In the rubber composition, the content of the tetrazine-based compounds (total amount of the tetrazine-based compounds) is preferably 0.2 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy and fracture resistance can be obtained.

[0429] (fine particle zinc carrier) The rubber composition may be blended with a particulate zinc carrier in which zinc oxide fine particles or basic zinc carbonate fine particles are supported on the surface of silicate particles. As the particulate zinc carrier, the same ones as those described above can be used.

[0430] In the rubber composition, the content of the zinc microparticle carrier is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.6 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 2.0 parts by mass or less, more preferably 1.8 parts by mass or less, and even more preferably 1.6 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance of fuel economy and fracture resistance can be obtained.

[0431] (Amide compounds) The rubber composition preferably contains an amide compound. As the amide compound, the same amide compounds as those described above can be used.

[0432] In the rubber composition, the content of the amide compound per 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and further preferably 2.5 parts by mass or less. By keeping the content within the above range, good overall performance in terms of fuel economy and fracture resistance tends to be obtained.

[0433] (sulfur) The rubber composition preferably contains sulfur. As the sulfur, the same sulfur as described above can be used.

[0434] In the rubber composition, the sulfur content is preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, and even more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 4.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy and fracture resistance can be obtained.

[0435] (Vulcanization accelerator) The rubber composition preferably contains a vulcanization accelerator. As the vulcanization accelerator, the same vulcanization accelerators as those described above can be used. Among them, sulfenamide-based vulcanization accelerators and guanidine-based vulcanization accelerators are preferred, and guanidine-based vulcanization accelerators are more preferred.

[0436] In the rubber composition, the content of the vulcanization accelerator is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.2 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy and fracture resistance can be obtained.

[0437] (Other ingredients) The rubber composition may further contain the above-mentioned wax, antioxidant, stearic acid, zinc oxide, and other compounding agents (organic crosslinking agent, etc.).

[0438] The rubber composition can be produced by the same method as for the above-mentioned rubber composition. A tire having the base tread can be manufactured in the same manner as the tire described above.

[0439] Examples of the tire having the base tread include pneumatic tires and airless (solid) tires, with pneumatic tires being preferred.

[0440] 〔breaker〕 (Rubber component) The present invention is a tire having the following breakers (1) to (3). Since a specific natural rubber derived from Russian dandelion is used in combination with carbon black and / or silica, the overall performance of fuel economy and fracture resistance is significantly (synergistically) improved.

[0441] (1) A first tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, the natural rubber having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, and carbon black and / or silica.

[0442] (2) A second tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, the natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight average molecular weight range of Mw of 5 million to 50 million of 130 nm or more, and carbon black and / or silica.

[0443] (3) A third tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line in a weight average molecular weight region of 5 million to 50 million in a plot of the common logarithm of the weight average molecular weight Mw (logMw) versus the common logarithm of the radius of gyration Rz of the polymer (logRz) having a slope of 0.25 or more.

[0444] The reason (mechanism) why the overall performance of excellent fuel economy and fracture resistance is significantly (synergistically) improved is not necessarily clear, but is presumed to be as follows. The specific Russian dandelion-derived natural rubber of the present application has a higher Mw and contains a larger amount of high molecular weight components than Hevea-derived natural rubber, which increases the breaking strength of the rubber. Furthermore, the Russian dandelion-derived natural rubber has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, which increases the Rz of the polymer. Therefore, the higher Rz of the polymer increases entanglement between polymers, and the higher probability of contact between the polymer and the filler increases interaction with the filler, improving reinforcing properties and breaking resistance.

[0445] Furthermore, the specific Russian dandelion-derived natural rubber of the present application has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, resulting in fewer free molecular ends and therefore fewer components that cause hysteresis loss, resulting in excellent low heat generation.

[0446] It is presumed that the combined use of such natural rubber derived from Russian dandelion with carbon black and / or silica will result in a significant (synergistic) improvement in the overall performance of fuel economy and fracture resistance.

[0447] The natural rubber derived from the Russian dandelion in the first to third tires is the same as the natural rubber derived from the Russian dandelion described above.

[0448] In the rubber composition, the content of the Russian dandelion-derived natural rubber is preferably 30% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, particularly preferably 90% by mass or more, and may be 100% by mass, based on 100% by mass of the rubber component. By keeping the content within the above range, the overall performance of fuel economy and fracture resistance is significantly improved.

[0449] The rubber composition may contain other rubber components in addition to the Russian dandelion-derived natural rubber. Examples of the other rubber components include those similar to those described above.

[0450] (Carbon Black) The rubber composition contains carbon black. As the carbon black, the same carbon black as described above can be used.

[0451] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 30 m 2 / g or more, more preferably 50m 2 / g or more, more preferably 65m 2 / g or more. In addition, the N2SA is preferably 150m 2 / g or less, more preferably 120m 2 / g or less, more preferably 100m 2 By setting the N2SA of carbon black to the lower limit or higher, excellent fracture resistance and other properties tend to be obtained. By setting it to the upper limit or lower, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0452] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 30 ml / 100 g or more, more preferably 50 ml / 100 g or more, and even more preferably 60 ml / 100 g or more. The DBP is preferably 150 ml / 100 g or less, more preferably 110 ml / 100 g or less, and even more preferably 90 ml / 100 g or less. By setting it to the lower limit or more, excellent fracture resistance and the like tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0453] In the rubber composition, the carbon black content is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 120 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 80 parts by mass or less. By making the content equal to or more than the lower limit, good fracture resistance and the like tend to be obtained. By making the content equal to or less than the upper limit, good fuel economy tends to be obtained.

[0454] (silica) The rubber composition contains silica. As the silica, the same silica as described above can be used.

[0455] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 20 m 2 / g or more, more preferably 30m 2 / g or more, more preferably 40m 2 / g or more. In addition, the N2SA is preferably 200m 2 / g or less, more preferably 150m 2 / g or less, more preferably 120m 2 / g or less. By making it equal to or more than the lower limit, excellent fracture resistance and the like tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0456] In the rubber composition, the content of silica (total amount of various silicas) is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 40 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 150 parts by mass or less, more preferably 120 parts by mass or less, and even more preferably 100 parts by mass or less. By making it equal to or more than the lower limit, excellent fracture resistance performance tends to be obtained. By making it equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0457] In the rubber composition, the total content of carbon black and silica is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 50 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 80 parts by mass or less. By making the content equal to or more than the lower limit, excellent fracture resistance and the like tend to be obtained. By making the content equal to or less than the upper limit, good silica dispersibility and excellent fuel economy tend to be obtained.

[0458] (Silane coupling agent) When the rubber composition contains silica, it is preferable to contain a silane coupling agent together with the silica. As the silane coupling agent, the same silane coupling agent as described above can be used. In addition, the mercapto-based silane coupling agent described above can also be suitably used.

[0459] When the rubber composition contains a silane coupling agent, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of silica. The content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By making the content equal to or more than the lower limit, the effect of improving dispersibility tends to be sufficiently obtained. By making the content equal to or less than the upper limit, the coupling effect tends to be sufficient, and good reinforcement tends to be obtained.

[0460] (Liquid plasticizer) The rubber composition may contain a liquid plasticizer (a plasticizer that is in a liquid state at room temperature (25° C.)). As the liquid plasticizer, the same liquid plasticizers as those described above can be used.

[0461] In the rubber composition, the content of the liquid plasticizer is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, per 100 parts by mass of the rubber component. By making the content equal to or more than the lower limit, good processability tends to be obtained. The upper limit is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less. By making the content equal to or less than the upper limit, good fracture resistance and the like tend to be obtained. The content of the liquid plasticizer includes the amount of oil (extending oil) contained in the rubber (oil-extended rubber). The content of the oil is also preferably in a similar range.

[0462] (Organic Cobalt Acid) The rubber composition preferably contains an organic acid cobalt, which acts to crosslink the rubber and the steel breaker, and thus the rubber composition contains an organic acid cobalt, which can improve the adhesion between the steel breaker and the rubber.

[0463] Examples of the organic acid cobalt include cobalt stearate, cobalt naphthenate, cobalt neodecanoate, boron 3 cobalt neodecanoate, cobalt abitienate, etc. Among these, cobalt stearate is preferred because it is excellent in processability (viscosity) and the vulcanization reaction easily proceeds.

[0464] In the rubber composition, the content of the organic acid cobalt is preferably 0.05 parts by mass or more, more preferably 0.08 parts by mass or more, calculated as the amount of cobalt metal, per 100 parts by mass of the rubber component. The content is preferably 0.50 parts by mass or less, more preferably 0.30 parts by mass or less, and even more preferably 0.20 parts by mass or less. By keeping the content within the above range, the adhesion between the steel breaker and the rubber becomes sufficient, and good crack growth resistance and the like tend to be obtained.

[0465] (Zinc Oxide) The rubber composition preferably contains zinc oxide. As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., and the like.

[0466] In the rubber composition, the content of zinc oxide is preferably 3.0 parts by mass or more, more preferably 5.0 parts by mass or more, and even more preferably 6.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 15.0 parts by mass or less, more preferably 12.0 parts by mass or less, and even more preferably 10.0 parts by mass or less. By keeping the content within the above range, the overall performance of fuel economy and fracture resistance is significantly improved.

[0467] (sulfur) The rubber composition preferably contains sulfur. As the sulfur, the same sulfur as described above can be used.

[0468] In the rubber composition, the sulfur content is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, and even more preferably 3.0 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 10.0 parts by mass or less, more preferably 8.0 parts by mass or less, and even more preferably 6.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy and fracture resistance can be obtained.

[0469] (Vulcanization accelerator) The rubber composition preferably contains a vulcanization accelerator. As the vulcanization accelerator, the same vulcanization accelerators as those described above can be used. Among them, sulfenamide-based vulcanization accelerators and guanidine-based vulcanization accelerators are preferred, and sulfenamide-based vulcanization accelerators are more preferred.

[0470] In the rubber composition, the content of the vulcanization accelerator is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy and fracture resistance can be obtained.

[0471] (Other ingredients) The rubber composition may further contain the same solid resins as those described above, farnesene-based resins, tetrazine-based compounds, fine zinc particles, amide compounds, waxes, antioxidants, stearic acid, and other compounding agents (such as organic crosslinking agents).

[0472] The rubber composition can be produced by the same method as for the above-mentioned rubber composition. A tire having the breaker can be manufactured in the same manner as the tire described above.

[0473] Examples of the tire having the breaker include pneumatic tires and airless (solid) tires, with pneumatic tires being preferred.

[0474] [Sidewall] (Rubber component) The present invention provides a tire having a sidewall as described below in (1) to (3). Since a specific natural rubber derived from Russian dandelion is used in combination with carbon black and / or silica, the overall performance of fuel economy and flex crack growth resistance is significantly (synergistically) improved.

[0475] (1) A first tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, the natural rubber having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, and carbon black and / or silica.

[0476] (2) A second tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, the natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of the polymer in the weight average molecular weight range of Mw of 5 million to 50 million of 130 nm or more, and carbon black and / or silica.

[0477] (3) A third tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line in a weight average molecular weight region of 5 million to 50 million in a plot of the common logarithm of the weight average molecular weight Mw (logMw) versus the common logarithm of the radius of gyration Rz of the polymer (logRz) having a slope of 0.25 or more.

[0478] The reason (mechanism) why the overall performance of excellent fuel economy and flex crack growth resistance is significantly (synergistically) improved is not necessarily clear, but is presumed to be as follows. The specific Russian dandelion-derived natural rubber of the present application has a higher Mw and contains a larger amount of high molecular weight components than Hevea-derived natural rubber, which increases the breaking strength of the rubber. Furthermore, the Russian dandelion-derived natural rubber has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, which increases the Rz of the polymer. Therefore, the higher Rz of the polymer increases entanglement between polymers, and the higher probability of contact between the polymer and the filler increases interaction with the filler, improving reinforcing properties and resistance to flex crack growth.

[0479] Furthermore, the specific Russian dandelion-derived natural rubber of the present application has a lower degree of branching and contains more linear polymers than Hevea-derived natural rubber, resulting in fewer free molecular ends and therefore fewer components that cause hysteresis loss, resulting in excellent low heat generation.

[0480] It is presumed that the combined use of such Russian dandelion-derived natural rubber with carbon black and / or silica will result in a significant (synergistic) improvement in the overall performance of fuel economy and flex crack growth resistance.

[0481] The natural rubber derived from the Russian dandelion in the first to third tires is the same as the natural rubber derived from the Russian dandelion described above.

[0482] In the rubber composition, the content of the Russian dandelion-derived natural rubber is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. By keeping the content within the above range, the overall performance of fuel economy and flex crack growth resistance is significantly improved.

[0483] The rubber composition may contain other rubber components in addition to the Russian dandelion-derived natural rubber. Examples of the other rubber components include those similar to those described above.

[0484] The rubber composition may contain other rubber components together with the Russian dandelion-derived natural rubber. Examples of the other rubber components include those similar to those described above. The rubber components may be either unmodified or modified rubber. Among them, BR is preferred from the viewpoint of overall performance of fuel economy and resistance to flex crack growth.

[0485] The BR is not particularly limited, and for example, the same BR as described above can be used.

[0486] In the rubber composition, the content of BR is preferably 10% by mass or more, more preferably 35% by mass or more, and even more preferably 50% by mass or more, based on 100% by mass of the rubber component. The upper limit is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. By keeping the content within the above range, the overall performance of fuel economy and flex crack growth resistance is significantly improved.

[0487] (Carbon Black) The rubber composition contains carbon black. As the carbon black, the same carbon black as described above can be used.

[0488] The nitrogen adsorption specific surface area (N2SA) of the carbon black is preferably 20 m 2 / g or more, more preferably 30m 2 / g or more, more preferably 35m 2 / g or more. In addition, the N2SA is preferably 80m 2 / g or less, more preferably 65m 2 / g or less, more preferably 55m 2 By setting the N2SA of carbon black to the lower limit or more, excellent resistance to flex crack growth, etc., tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility and excellent fuel economy tend to be obtained.

[0489] The dibutyl phthalate oil absorption (DBP) of the carbon black is preferably 50 ml / 100 g or more, more preferably 80 ml / 100 g or more, and even more preferably 100 ml / 100 g or more. The DBP is preferably 150 ml / 100 g or less, more preferably 130 ml / 100 g or less, and even more preferably 120 ml / 100 g or less. By setting it to the lower limit or more, excellent flex crack growth resistance and the like tend to be obtained. By setting it to the upper limit or less, good carbon black dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0490] In the rubber composition, the carbon black content is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 60 parts by mass or less. By making the content equal to or more than the lower limit, good flex crack growth resistance and the like tend to be obtained. By making the content equal to or less than the upper limit, good fuel economy tends to be obtained.

[0491] (silica) The rubber composition contains silica. As the silica, the same silica as described above can be used.

[0492] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 20 m 2 / g or more, more preferably 30m 2 / g or more, more preferably 40m 2 / g or more. In addition, the N2SA is preferably 200m 2 / g or less, more preferably 150m 2 / g or less, more preferably 120m 2 / g or less. By making it equal to or more than the lower limit, excellent resistance to flex crack growth, etc. tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0493] In the rubber composition, the content of silica (total amount of various silicas) is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 40 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 150 parts by mass or less, more preferably 120 parts by mass or less, and even more preferably 100 parts by mass or less. By making it equal to or more than the lower limit, excellent flex crack growth resistance and the like tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0494] In the rubber composition, the total content of carbon black and silica is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 45 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 80 parts by mass or less. By making it equal to or more than the lower limit, excellent flex crack growth resistance and the like tend to be obtained. By making it equal to or less than the upper limit, good silica dispersibility tends to be obtained, and excellent fuel economy tends to be obtained.

[0495] (Silane coupling agent) When the rubber composition contains silica, it is preferable to contain a silane coupling agent together with the silica. As the silane coupling agent, the same silane coupling agent as described above can be used. In addition, the mercapto-based silane coupling agent described above can also be suitably used.

[0496] When the rubber composition contains a silane coupling agent, the content is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of silica. The content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By making the content equal to or more than the lower limit, the effect of improving dispersibility tends to be sufficiently obtained. By making the content equal to or less than the upper limit, the coupling effect tends to be sufficient, and good reinforcement tends to be obtained.

[0497] (Liquid plasticizer) The rubber composition may contain a liquid plasticizer (a plasticizer that is in a liquid state at room temperature (25° C.)). As the liquid plasticizer, the same liquid plasticizers as those described above can be used.

[0498] In the rubber composition, the content of the liquid plasticizer is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, based on 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, good processability tends to be obtained. The upper limit is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less. By making it equal to or less than the upper limit, good flex crack growth resistance and the like tend to be obtained. The content of the liquid plasticizer also includes the amount of oil (extending oil) contained in the rubber (oil-extended rubber). The content of the oil is also preferably in a similar range.

[0499] (Solid Resin) The rubber composition may contain a solid resin (a polymer that is in a solid state at room temperature (25° C.)). As the solid resin, the same solid resin as described above can be used.

[0500] In the rubber composition, the content of the solid resin is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less. When the content is within the above range, good overall performance in terms of fuel economy and flex crack growth resistance tends to be obtained.

[0501] (sulfur) The rubber composition preferably contains sulfur. As the sulfur, the same sulfur as described above can be used.

[0502] In the rubber composition, the content of sulfur is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.2 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 5.0 parts by mass or less, more preferably 4.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy and flex crack growth resistance can be obtained.

[0503] (Vulcanization accelerator) The rubber composition preferably contains a vulcanization accelerator. As the vulcanization accelerator, the same vulcanization accelerators as those described above can be used, among which sulfenamide-based vulcanization accelerators and guanidine-based vulcanization accelerators are preferred.

[0504] In the rubber composition, the content of the vulcanization accelerator is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, based on 100 parts by mass of the rubber component. The upper limit is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less. By keeping the content within the above range, there is a tendency that good overall performance in terms of fuel economy and flex crack growth resistance can be obtained.

[0505] (Other ingredients) The rubber composition may further contain the farnesene-based resin, tetrazine-based compound, fine zinc particle carrier, amide compound, wax, antioxidant, stearic acid, zinc oxide, and other compounding agents (organic crosslinking agent, etc.) as described above.

[0506] The rubber composition can be produced by the same method as for the above-mentioned rubber composition. A tire having the above sidewall can be manufactured in the same manner as the tire described above.

[0507] Examples of the tire having the sidewall include pneumatic tires and airless (solid) tires, with pneumatic tires being preferred. EXAMPLES

[0508] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.

[0509] <Production Example 1: Production of Russian dandelion-derived natural rubber A, B, and C> Russian dandelion-derived natural rubbers A, B, and C were prepared using the extraction methods described in U.S. Patent Publications US2019 / 0048101A1 and US2019 / 0046895A1.

[0510] For the Russian dandelion-derived natural rubbers A to C, Hevea-derived natural rubber (TSR20), and synthetic isoprene rubber (synthetic IR: JSR IR2200) produced in the above Production Examples, Mw and Mw / Mn measured by FFF-MALS, polymer Rz, average polymer Rz in the Mw range of 5 million to 50 million, and the slope of the linear regression line in the logRz plot against logMw (Mw range of 5 million to 50 million) are shown in Table 1. The measurement methods for each are as follows.

[0511] (Measurement of Mw, Mn, and Rz of polymers by FFF-MALS) A rubber sample was added to THF so that the rubber concentration in the solution was 0.2 mass%. After shaking for one week, the resulting solution was filtered using a PTFE filter (pore size 1.0 or 5.0 μm). The filtrate was measured and analyzed by FFF-MALS. The specifications of the FFF instrument, MALS detector, and RI detector used are as follows: FFF device: Postnova TF2000 (measurement conditions: THF was used as the mobile phase, and the flow rate was 0.3 mL / min) MALS detector: Postnova PN3150 (measurement conditions: Detected at a total of 21 angles from 7° to 168°) RI detector: Postnova PN3621 (measurement conditions: detector temperature was 37°C) How to connect the piping of the equipment: FFF equipment - MALS detector - RI detector in that order.

[0512] (Measurement of the average Rz value of polymers in the range of Mw 5 million to 50 million) Based on the Mw and Rz values ​​obtained by FFF-MALS, the average Rz value of the polymer in the range of Mw 5 million to 50 million was calculated. Note that (Mw, Rz) data was acquired every 2 seconds by FFF-MALS, and a total of 300 to 400 pieces of data were obtained.

[0513] (Measurement of the slope of the linear regression line in the region of Mw 5 million to 50 million on the logMw-logRz plot) A logMw-logRz plot was created using each Mw and Rz obtained by FFF-MALS. A linear regression line was calculated using the least squares method for the data in the Mw range of 5 million to 50 million, and the slope was determined.

[0514] [Table 1]

[0515] <Production Example 2: Synthesis of zinc-supported fine particles> 91.5g of zinc oxide was added to 847ml of 5.5% by mass calcined clay aqueous suspension and thoroughly stirred. Next, 330g of 10% by mass sodium carbonate aqueous solution and 340g of 10% by mass zinc chloride aqueous solution were added and further stirred. 30% by mass carbon dioxide gas was blown into the mixture until the pH became 7 or less, and basic zinc carbonate was precipitated on the surface of the calcined clay to synthesize a zinc-supported microparticle. The mixture was then dehydrated, dried, and pulverized to obtain a zinc-supported microparticle. The BET specific surface area of ​​the zinc microparticle carrier is 50m 2 / g. In addition, in the fine particle zinc support, basic zinc carbonate was supported on the calcined clay in an amount of 45 mass% as metallic zinc. Therefore, the BET specific surface area of ​​the supported basic zinc carbonate was 60 m 2 / g.

[0516] <Production Examples 3-1 and 3-2: Production of Carbon Black B and C> A carbon black reactor was used in which a combustion zone with an inner diameter of 1,100 mm and a length of 1,700 mm and equipped with an air inlet duct and a combustion burner, a feedstock introduction zone consisting of a narrow-diameter section with an inner diameter of 175 mm and a length of 1,050 mm connected to the combustion zone and with a feedstock nozzle penetrating from the periphery, and a rear reaction zone with an inner diameter of 400 mm and a length of 3,000 mm and equipped with a quench device were successively connected. Carbon black was produced under the conditions shown in Table 2 using D heavy oil as the fuel oil and creosote oil as the feedstock hydrocarbon (feedstock oil). Next, the produced carbon black was subjected to a heat treatment under the conditions shown in Table 2 without oxygen flowing (under a nitrogen gas atmosphere). Various properties of carbon blacks B and C obtained in Production Examples 3-1 and 3-2 are shown in Table 3.

[0517] [Table 2]

[0518] [Table 3]

[0519] <Production Example 4-1 (Synthesis of Conjugated Diene Polymer)> A catalyst composition (iodine atom / lanthanoid-containing compound (molar ratio)=2.0) was obtained by reacting and aging a cyclohexane solution containing 0.18 mmol of neodymium versatate, a toluene solution containing 3.6 mmol of methylalumoxane, a toluene solution containing 6.7 mmol of diisobutylaluminum hydride, and a toluene solution containing 0.36 mmol of trimethylsilyl iodide with 0.90 mmol of 1,3-butadiene at 30° C. for 60 minutes. Then, 2.4 kg of cyclohexane and 300 g of 1,3-butadiene were put into a 5 L autoclave purged with nitrogen. The catalyst composition was then put into the autoclave and polymerized at 30° C. for 2 hours to obtain a polymer solution. The reaction conversion rate of the put-in 1,3-butadiene was almost 100%.

[0520] Here, in order to measure various physical properties of the conjugated diene polymer (hereinafter also referred to as "polymer"), i.e., the one before modification, 200 g of the polymer solution was extracted from the above polymer solution, and a methanol solution containing 1.5 g of 2,4-di-tert-butyl-p-cresol was added to this polymer solution to terminate the polymerization reaction, and then the solvent was removed by steam stripping and dried with a roll at 110°C, and the obtained dried product was used as a polymer.

[0521] The various physical properties of the polymer are Mooney viscosity (ML 1+4 , 100°C) was 12, the molecular weight distribution (Mw / Mn) was 1.6, the cis-1,4-bond content was 99.2 mass%, and the 1,2-vinyl bond content was 0.21 mass%.

[0522] <Production Example 4-2 (Synthesis of modified conjugated diene polymer)> In order to obtain a modified conjugated diene polymer (hereinafter also referred to as a "modified polymer"), the following treatment was performed on the polymer solution of the conjugated diene polymer of Production Example 4-1. A toluene solution containing 1.71 mmol of 3-glycidoxypropyltrimethoxysilane was added to the polymer solution kept at a temperature of 30°C, and the mixture was reacted for 30 minutes to obtain a reaction solution. Then, a toluene solution containing 1.71 mmol of 3-aminopropyltriethoxysilane was added to the reaction solution, and the mixture was stirred for 30 minutes. Next, a toluene solution containing 1.28 mmol of tetraisopropyl titanate was added to the reaction solution, and the mixture was stirred for 30 minutes. After that, a methanol solution containing 1.5 g of 2,4-di-tert-butyl-p-cresol was added to terminate the polymerization reaction, and the solution was made into a modified polymer solution. The yield was 2.5 kg. Next, 20 L of an aqueous solution adjusted to pH 10 with sodium hydroxide was added to the modified polymer solution, and the solution was subjected to a condensation reaction at 110°C for 2 hours while removing the solvent. Thereafter, it was dried with a roll at 110° C., and the resulting dried material was used as a modified polymer.

[0523] The physical properties of the modified polymer are Mooney viscosity (ML 1+4 ,125℃) was 46, molecular weight distribution (Mw / Mn) was 2.4, cold flow value was 0.3 mg / min, stability over time was 2, and glass transition temperature was -106℃.

[0524] <Production Example 5: Production of oil-extended diene polymer (SBR3)> Two autoclaves with an internal volume of 10 liters, an inlet at the bottom and an outlet at the top, and an agitator and a jacket were connected in series as reactors, and butadiene, styrene, and cyclohexane were mixed in a predetermined ratio. This mixed solution was passed through a dehydration column filled with activated alumina, and after mixing with n-butyllithium in a static mixer to remove impurities, it was continuously fed from the bottom of the first reactor, and further 2,2-bis(2-oxolanyl)propane as a polar substance and n-butyllithium as a polymerization initiator were continuously fed from the bottom of the first reactor at a predetermined rate, and the temperature inside the reactor was maintained at 95°C. The polymer solution was continuously extracted from the head of the reactor and fed to the second reactor. The temperature of the second reactor was kept at 95°C, and a mixture of tetraglycidyl-1,3-bisaminomethylcyclohexane (monomer) as a modifier and an oligomer component was continuously added as a 1000-fold diluted solution of cyclohexane at a predetermined rate to carry out a modification reaction. This polymer solution was continuously withdrawn from the reactor, and an antioxidant was continuously added using a static mixer. Furthermore, 25 parts by mass of Japan Energy extender oil NC140 per 100 parts by mass of the polymer was added to this polymer solution and mixed, and then the solvent was removed to obtain the desired oil-extended modified diene polymer (SBR3).

[0525] Various chemicals used in the examples and comparative examples will be collectively described below. (Rubber component) Russian dandelion-derived natural rubber A to C: Production Example 1 Hevea-derived natural rubber: TSR20 Synthetic isoprene rubber (synthetic IR): JSR IR2200 Modified conjugated diene polymer: Production Example 4-2 SBR1: SBR1502 manufactured by JSR Corporation (styrene content 23.5% by mass, vinyl content 16% by mass, non-oil extended) SBR2: SLR6430 manufactured by Dow Chemical (styrene content 40% by mass, vinyl content 24% by mass, Mw 1.36 million, contains 37.5 parts by mass of oil per 100 parts by mass of rubber solids) SBR3: Modified SBR synthesized in Production Example 5 (styrene content 38% by mass, vinyl content 39% by mass, Mw 800,000, Tg -25°C, oil-extended rubber containing 25 parts by mass of oil per 100 parts by mass of rubber solids) BR: BR150B (cis content 98% by mass) manufactured by Ube Industries, Ltd. (silica) Silica A: 115GR (N2SA115m) manufactured by Solvay Japan Co., Ltd. 2 / g) Silica B: VN3 (N2SA175m manufactured by Evonik 2 / g) Silica C: Evonik 9100GR (N2SA235m 2 / g) Silica D: Ultrasil 360 (N2SA50m) manufactured by Evonik Degussa 2 / g) (Silane coupling agent) Silane coupling agent A: Si69 (bis(3-triethoxysilylpropyl)tetrasulfide) manufactured by Evonik Degussa Silane coupling agent B: NXT (3-octanoylthiopropyltriethoxysilane) manufactured by Momentive Silane coupling agent C: NXT-Z45 manufactured by Momentive (a copolymer of bond unit A and bond unit B (bond unit A: 55 mol %, bond unit B: 45 mol %)) (Carbon Black) Carbon black A: Diablack N339 (N2SA96m) manufactured by Mitsubishi Chemical Corporation 2 / g, DBP absorption 124ml / 100g) Carbon black B: Preparation Example 3-1 Carbon black C: Preparation Example 3-2 Carbon black D: Diablack N326 (N2SA84m) manufactured by Mitsubishi Chemical Corporation 2 / g, DBP oil absorption 74ml / 100g) Carbon black E: Diablack N550 (N2SA41m) manufactured by Mitsubishi Chemical Corporation 2 / g, DBP absorption 115ml / 100g) (Solid Resin) Resin A: YS Resin PX1150N (polyterpene (β-pinene resin), softening point 115°C) manufactured by Yasuhara Chemical Co., Ltd. Resin B: YS Polystar T160 (terpene phenol resin, softening point 160°C) manufactured by Yasuhara Chemical Co., Ltd. Resin C: Maruzen Petrochemical Co., Ltd.'s Marukaretzu M-890A (dicyclopentadiene resin, softening point 105°C) Resin D: Pine Crystal KR-85 (rosin-based resin, softening point 80-87°C) manufactured by Arakawa Chemical Industries, Ltd. Resin E: SYLVARES SA85 manufactured by Arizona Chemical Co. (copolymer of α-methylstyrene and styrene, softening point 85°C) (Liquid plasticizer) Oil: X-140 (aromatic process oil) manufactured by JXTG Energy Corporation (Farnesene resin) Farnesene resin A: KB-101 manufactured by Kuraray Co., Ltd. (farnesene homopolymer, Mw 10000, melt viscosity 0.7 Pa·s, Tg -72°C) Farnesene resin B: FSR-221 manufactured by Kuraray Co., Ltd. (farnesene-styrene copolymer, Mw 10,000, copolymerization ratio by mass of farnesene / styrene = 77 / 23, melt viscosity 5.7 Pa·s, Tg -54°C) Farnesene resin C: FBR-746 manufactured by Kuraray Co., Ltd. (farnesene-butadiene copolymer, Mw 100,000, copolymerization ratio by mass of farnesene / butadiene = 60 / 40, melt viscosity 603 Pa·s, Tg -78°C) (Anti-aging agent) Anti-aging agent 1: Antigen 3C (N-phenyl-N'-isopropyl-p-phenylenediamine) manufactured by Sumitomo Chemical Co., Ltd. Antioxidant 2: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. (Stearic acid) Stearic acid: Camellia made by NOF Corporation (Organic Cobalt Acid) Cobalt stearate: Cost-F (cobalt content 9.5% by mass) manufactured by Dainippon Ink and Chemicals, Inc. (Zinc Oxide) Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. (fine particle zinc carrier) Fine particle zinc carrier: Production Example 2 (wax) Wax: Sunnock N (paraffin wax) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. (Amide compounds) Amide compound: WB16 manufactured by Struktol (a mixture of fatty acid calcium, fatty acid amides and fatty acid amide esters, ash content 4.5%) (sulfur) Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Co., Ltd. (Vulcanization accelerator) Vulcanization accelerator 1: Noccela CZ (N-cyclohexyl-2-benzothiazolyl sulfenamide (CBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator 2: Noccelaer D (1,3-diphenylguanidine (DPG)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator 3: Noccela DZ (N,N'-dicyclohexyl-2-benzothiazolyl sulfenamide (DZ)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. (Tetrazine compounds) Tetrazine compound A: a compound represented by the above formula (1-1-1) Tetrazine compound B: a compound represented by the above formula (1-2-1)

[0526] <Examples and Comparative Examples> [Heavy-duty tires] According to the formulations shown in Tables 4-1 to 4-8, materials other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain a sheet-shaped unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized in a 0.5 mm thick mold at 150° C. for 30 minutes to obtain a sheet-like vulcanized rubber composition. In addition, the obtained unvulcanized rubber composition was molded into the shape of a cap tread, and laminated together with other tire components on a tire building machine to form an unvulcanized tire. The unvulcanized tire was then vulcanized at 150°C for 30 minutes to produce a test tire (size: 11R22.5).

[0527] The obtained vulcanized rubber compositions (vulcanized rubber sheets) and test tires were evaluated as follows. The results are shown in Tables 4-1 to 4-8. The reference comparative examples (index 100) are Comparative Examples 1-1a to 1-8a.

[0528] <Wear resistance> The test tires were fitted to a domestically produced 2-D vehicle, and the tire tread depth was measured after 50,000 km of driving. The distance traveled when the tire tread depth was reduced by 1 mm was calculated and expressed as an index using the following formula. The higher the index, the better the wear resistance. (Wear resistance index) = (mileage for each compound) / (mileage for standard comparative example) x 100

[0529] <Wet grip performance> The wet grip performance of the test tires was evaluated by the following tests. (WET turning performance index) Location: Sumitomo Rubber Industries, Ltd. Okayama Test Course Method: The lap time when completing one lap around a course with a radius of 30m in wet conditions was expressed as the reciprocal of the ratio to the standard comparison example. The standard comparison example is set to 100, and the higher the value, the better the wet grip performance.

[0530] <Fuel-efficient> A rectangular test piece having a width of 1 mm or 2 mm and a length of 40 mm was punched out from the sheet-like vulcanized rubber composition and used for the test. The loss tangent (tan δ(50°C)) of the test piece was measured at a temperature of 50°C under conditions of a strain of 1% and a frequency of 10 Hz using a viscoelasticity measuring device (manufactured by Ueshima Seisakusho Co., Ltd.), and the loss tangent was expressed as an index, with the reciprocal of tan δ of the reference comparative example being set at 100. The higher the index, the better the fuel economy.

[0531] [Table 4-1]

[0532] [Table 4-2]

[0533] [Table 4-3]

[0534] [Table 4-4]

[0535] [Table 4-5]

[0536] [Table 4-6]

[0537] [Table 4-7]

[0538] [Table 4-8]

[0539] As can be seen from each table, in the examples in which the specific natural rubber derived from Russian dandelion of the present invention was used in combination with carbon black in a specified blend, the overall performance of fuel economy, abrasion resistance and wet grip performance was significantly improved.

[0540] <Examples and Comparative Examples> [All-season tires] According to the compounding recipes shown in Tables 5-1 to 5-10, chemicals other than sulfur and vulcanization accelerator were kneaded using a 1.7 L Banbury mixer. Next, sulfur and vulcanization accelerator were added to the kneaded mixture using a roll and kneaded to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was molded into a sheet of 2.1 mm and vulcanized at 150° C. for 30 minutes to obtain a vulcanized rubber composition of 2 mm. In addition, the obtained unvulcanized rubber composition was molded into the shape of a cap tread, and laminated together with other tire components on a tire building machine to form an unvulcanized tire. The unvulcanized tire was then vulcanized at 150°C for 30 minutes to produce a test tire (all-season tire).

[0541] The obtained vulcanized rubber compositions (vulcanized rubber sheets) and test tires were evaluated as follows. The results are shown in Tables 5-1 to 5-10. The reference comparative examples (index 100) are Comparative Examples 2-1a to 2-10a.

[0542] <Wear resistance> Each test tire was fitted to a domestically produced FF vehicle, and the tire tread depth was measured after 8,000 km of driving. The distance traveled when the tire tread depth decreased by 1 mm was calculated and indexed using the following formula. The higher the index, the better the wear resistance. Abrasion resistance index = (mileage when tire tread of each compound is reduced by 1 mm) / (mileage when tire tread of standard comparative example is reduced by 1 mm) x 100

[0543] <Wet grip performance> Each test tire was fitted to all wheels of a vehicle (domestic FF 2000cc), and the braking distance from an initial speed of 100km / h on a wet asphalt road was calculated. The results were expressed as an index, with the higher the number, the better the wet grip performance. The index was calculated using the following formula. (Wet grip performance index) = (braking distance of standard comparative example) / (braking distance of each compounding example) x 100

[0544] <Fuel-efficient> Using a rolling resistance tester, the rolling resistance of each test tire was measured when it was run with a rim (15x6JJ), internal pressure (230kPa), load (3.43kN), and speed (80km / h), and was expressed as an index with the reference comparative example being set at 100. The higher the index, the better (lower fuel consumption).

[0545] [Table 5-1]

[0546] [Table 5-2]

[0547] [Table 5-3]

[0548] [Table 5-4]

[0549] [Table 5-5]

[0550] [Table 5-6]

[0551] [Table 5-7]

[0552] [Table 5-8]

[0553] [Table 5-9]

[0554] [Table 5-10]

[0555] As can be seen from each table, the examples in which the specific Russian dandelion-derived natural rubber of this application, carbon black, and silica with a specific nitrogen adsorption specific surface area were used in combination in a specified blend showed significant improvements in overall fuel economy, abrasion resistance, and wet grip performance.

[0556] <Examples and Comparative Examples> [Summer tires] According to the compounding recipes shown in Tables 6-1 to 6-10, chemicals other than sulfur and vulcanization accelerator were kneaded using a 1.7 L Banbury mixer. Next, sulfur and vulcanization accelerator were added to the kneaded mixture using a roll and kneaded to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was molded into a sheet of 2.1 mm and vulcanized at 150° C. for 30 minutes to obtain a vulcanized rubber composition of 2 mm. In addition, the obtained unvulcanized rubber composition was molded into the shape of a cap tread, and was laminated together with other tire components on a tire building machine to form an unvulcanized tire. The unvulcanized tire was then vulcanized at 150°C for 30 minutes to produce a test tire (summer tire for passenger cars).

[0557] The obtained vulcanized rubber compositions (vulcanized rubber sheets) and test tires were evaluated as follows. The results are shown in Tables 6-1 to 6-10. The reference comparative examples (index 100) are Comparative Example 3-1a to Comparative Example 3-10a.

[0558] <Wear resistance> Each test tire was fitted to a domestically produced FF vehicle, and the tire tread depth was measured after 8,000 km of driving. The distance traveled when the tire tread depth decreased by 1 mm was calculated and indexed using the following formula. The higher the index, the better the wear resistance. Abrasion resistance index = (mileage when tire tread of each compound is reduced by 1 mm) / (mileage when tire tread of standard comparative example is reduced by 1 mm) x 100

[0559] <Wet grip performance> Each test tire was fitted to all wheels of a vehicle (domestic FF 2000cc), and the braking distance from an initial speed of 100km / h on a wet asphalt road was calculated. The results were expressed as an index, with the higher the number, the better the wet grip performance. The index was calculated using the following formula. (Wet grip performance index) = (braking distance of standard comparative example) / (braking distance of each compounding example) x 100

[0560] <Fuel-efficient> Using a rolling resistance tester, the rolling resistance of each test tire was measured when it was run with a rim (15x6JJ), internal pressure (230kPa), load (3.43kN), and speed (80km / h), and was expressed as an index with the reference comparative example being set at 100. The higher the index, the better (lower fuel consumption).

[0561] [Table 6-1]

[0562] [Table 6-2]

[0563] [Table 6-3]

[0564] [Table 6-4]

[0565] [Table 6-5]

[0566] [Table 6-6]

[0567] [Table 6-7]

[0568] [Table 6-8]

[0569] [Table 6-9]

[0570] [Table 6-10]

[0571] As can be seen from each table, the examples in which the specific Russian dandelion-derived natural rubber of this application, styrene-butadiene rubber with a specific styrene content, carbon black, and silica with a specific nitrogen adsorption specific surface area were used in combination in a specified blend showed significant improvements in overall performance in terms of fuel economy, abrasion resistance, and wet grip performance.

[0572] <Examples and Comparative Examples> [Studless tires] According to the compounding recipes shown in Tables 7-1 to 7-10, chemicals other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd., to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized at 170° C. for 10 minutes to obtain a vulcanized rubber composition. The unvulcanized rubber composition thus obtained was molded into the shape of a cap tread, and was laminated together with other tire components to prepare an unvulcanized tire. The tire was press-vulcanized at 170° C. for 10 minutes to obtain a test tire (size: 195 / 65R15).

[0573] The obtained vulcanized rubber compositions (vulcanized rubber sheets) and test tires were evaluated as follows. The results are shown in Tables 7-1 to 7-10. The reference comparative examples (index 100) are Comparative Example 4-1a to Comparative Example 4-10a.

[0574] <Wear resistance> The abrasion amount of the vulcanized rubber composition was measured using a Lambourn abrasion tester manufactured by Iwamoto Seisakusho Co., Ltd. under the conditions of a surface rotation speed of 50 m / min, an applied load of 3.0 kg, a sand drop amount of 15 g / min, and a slip ratio of 20%, and the reciprocal of the abrasion amount was calculated. The reciprocal of the abrasion amount of the reference comparative example was set to 100, and the reciprocals of the abrasion amounts of the other formulations were expressed as an index. The larger the index, the more excellent the abrasion resistance.

[0575] <Performance on snow and ice> Using each test studless tire, actual vehicle performance on ice was evaluated under the following conditions. The test was conducted at Sumitomo Rubber Industries' Nayoro test course in Hokkaido, where the temperature was 0 to -5°C. The test tires were fitted to a domestically produced 2000cc FR vehicle, and the stopping distance on ice required to stop the vehicle by applying the lock brakes at a speed of 30km / h was measured. Using a standard comparative example as a reference, the results were expressed as an index using the following formula. The higher the index, the better the performance on snow and ice. (Performance on snow and ice) = (stopping distance of standard comparison example) / (stopping distance of each compound) x 100

[0576] <Fuel-efficient> Using a rolling resistance tester, the rolling resistance was measured when the test studless tires were driven with rims (15x6JJ), internal pressure (230kPa), load (3.43kN), and speed (80km / h), and expressed as an index with the reference comparison example being set at 100. The higher the index, the lower the rolling resistance and the better the fuel efficiency.

[0577] [Table 7-1]

[0578] [Table 7-2]

[0579] [Table 7-3]

[0580] [Table 7-4]

[0581] [Table 7-5]

[0582] [Table 7-6]

[0583] [Table 7-7]

[0584] [Table 7-8]

[0585] [Table 7-9]

[0586] [Table 7-10]

[0587] As can be seen from each table, the examples in which the specific Russian dandelion-derived natural rubber of this application, the butadiene rubber with a specific cis-1,4-bond amount, carbon black, and silica with a specific nitrogen adsorption specific surface area were used in combination in a specified blend showed significant improvements in overall performance in terms of fuel efficiency, abrasion resistance, and performance on snow and ice.

[0588] <Examples and Comparative Examples> [Base tread] According to the formulations shown in Tables 8-1 to 8-10, materials other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized in a 0.5 mm thick mold at 170° C. for 20 minutes to obtain a vulcanized rubber composition. In addition, the obtained unvulcanized rubber composition was molded into the shape of a base tread, and was laminated together with other tire components on a tire building machine to form an unvulcanized tire. The tire was then vulcanized at 170°C for 12 minutes to produce a test tire (size: 195 / 65R15).

[0589] The obtained vulcanized rubber compositions (vulcanized rubber sheets) and test tires were evaluated as follows. The results are shown in Tables 8-1 to 8-10. The reference comparative examples (index 100) are Comparative Examples 5-1a to 5-10a.

[0590] <Breakdown resistance> A tensile test was carried out on the vulcanized rubber sheet (vulcanized rubber composition) using a No. 3 dumbbell in accordance with JIS K 6251 to measure the breaking strength (TB) and elongation at break (EB) (%). The value of TB x EB / 2 was taken as the breaking strength, and was expressed as an index with the breaking strength of the reference comparative example taken as 100. The higher the index, the better the breaking strength.

[0591] <Fuel-efficient> Using a rolling resistance tester, the rolling resistance was measured when the test tire was run with a rim (15x6JJ), internal pressure (230kPa), load (3.43kN), and speed (80km / h), and expressed as an index with the reference comparative example being set at 100. The higher the index, the lower the rolling resistance and the better the fuel efficiency.

[0592] [Table 8-1]

[0593]

Table 8-2

[0594]

Table 8-3

[0595]

Table 8-4

[0596]

Table 8-5

[0597]

Table 8-6

[0598]

Table 8-7

[0599]

Table 8-8

[0600]

Table 8-9

[0601]

Table 8-10

[0602] From each table, it can be seen that in the examples in which the specific natural rubber derived from Russian dandelion of this application, carbon black and silica were used in combination in a specified blend, the overall performance of fuel economy and fracture resistance was significantly improved.

[0603] <Examples and Comparative Examples> 〔breaker〕 According to the composition shown in Table 9, materials other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized in a 0.5 mm thick mold at 170° C. for 20 minutes to obtain a vulcanized rubber composition. Also, a steel cord was coated with the obtained unvulcanized rubber composition, which was then molded into a breaker shape, and then laminated with other tire components and vulcanized at 150° C. for 30 minutes to obtain a test tire.

[0604] The following evaluations were carried out on the obtained vulcanized rubber composition (vulcanized rubber sheet) and test tire. The results are shown in Table 9. The reference comparative example (index 100) is Comparative Example 6-1.

[0605] <Fuel-efficient> Using a rolling resistance tester, the rolling resistance was measured when the test tire was run with a rim (15x6JJ), internal pressure (230kPa), load (3.43kN), and speed (80km / h), and expressed as an index with the reference comparative example being set at 100. The higher the index, the lower the rolling resistance and the better the fuel efficiency.

[0606] <Breakdown resistance> The vulcanized rubber sheet was subjected to a tensile test using a No. 3 dumbbell in accordance with JIS K 6251 to measure the breaking strength (TB) and elongation at break (EB) (%). The value of TB x EB / 2 was taken as the breaking strength, and was expressed as an index with the breaking strength of the reference comparative example taken as 100. The higher the index, the better the breaking strength.

[0607] [Table 9]

[0608] As can be seen from the table, in the examples in which the specific natural rubber derived from Russian dandelion of the present invention was used in combination with carbon black and / or silica, the overall performance of fuel economy and fracture resistance was significantly improved.

[0609] <Examples and Comparative Examples> [Sidewall] According to the composition shown in Table 10, materials other than sulfur and vulcanization accelerator were kneaded using a 1.7 L Banbury mixer to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the obtained kneaded product, and the mixture was kneaded using an open roll to obtain an unvulcanized rubber composition. The obtained unvulcanized rubber composition was pressed in a 1 mm thick mold at 150° C. for 30 minutes to obtain a vulcanized rubber composition. In addition, the obtained unvulcanized rubber composition was molded into a sidewall shape, and was laminated together with other tire components on a tire building machine to form an unvulcanized tire. The tire was then vulcanized at 170°C for 12 minutes to produce a test tire (size: 195 / 65R15).

[0610] The vulcanized rubber composition (vulcanized rubber sheet) and the test tire obtained were subjected to the following evaluations. The results are shown in Table 10. The reference comparative example (index 100) is Comparative Example 7-1.

[0611] <Fuel-efficient> Using a rolling resistance tester, the rolling resistance was measured when the test tire was run with a rim (15x6JJ), internal pressure (230kPa), load (3.43kN), and speed (80km / h), and expressed as an index with the reference comparative example being set at 100. The higher the index, the lower the rolling resistance and the better the fuel efficiency.

[0612] <Flex crack growth resistance> Using a vulcanized rubber sheet (vulcanizate), samples were prepared based on JIS-K-6260 "Vulcanized rubber and thermoplastic rubber - Dematcia flex crack test method" and a flex crack growth test was conducted. The rubber sheet was bent by repeating 70% elongation 1 million times, and the length of the crack that occurred was measured. The reciprocal of the measured value (length) of the reference comparative example was set to 100 and expressed as an index. The larger the index, the more the crack growth was suppressed and the better the flex crack growth resistance.

[0613] [Table 10]

[0614] As can be seen from the table, in the examples in which the specific Russian dandelion-derived natural rubber of the present invention was used in combination with carbon black and / or silica, the overall performance of fuel economy and flex crack growth resistance was significantly improved.

Claims

1. A tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, carbon black and / or silica, and an organic acid cobalt.

2. A tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of a polymer in the weight average molecular weight range of 5 million to 50 million of 130 nm or more, carbon black and / or silica, and an organic acid cobalt.

3. A tire having a breaker made using a rubber composition containing natural rubber derived from Russian dandelion, carbon black and / or silica, and an organic acid cobalt, the rubber composition comprising: natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS, and a linear regression line having a slope of 0.25 or more in a region of a weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer.

4. The present invention has a breaker made of a rubber composition containing a natural rubber derived from Russian dandelion, the natural rubber having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, and carbon black, The rubber composition for a tire has a carbon black content of 3 to 120 parts by mass per 100 parts by mass of a rubber component.

5. The invention has a breaker made of a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of a polymer in a weight average molecular weight range of 5 million to 50 million of 130 nm or more, and carbon black; The rubber composition for a tire has a carbon black content of 3 to 120 parts by mass per 100 parts by mass of a rubber component.

6. the breaker is made using a rubber composition containing natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS, and a linear regression line in a region of a weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer, with a slope of 0.25 or more; and carbon black; The rubber composition for a tire has a carbon black content of 3 to 120 parts by mass per 100 parts by mass of a rubber component.

7. The present invention has a breaker made of a rubber composition containing silica and natural rubber derived from Russian dandelion, the natural rubber having a weight average molecular weight Mw of 5 million or more and a polymer radius of gyration Rz of 130 nm or more as measured by FFF-MALS, The rubber composition has a silica content of 20 parts by mass or more and 150 parts by mass or less based on 100 parts by mass of a rubber component.

8. The present invention has a breaker made of a rubber composition containing silica and natural rubber derived from Russian dandelion, the weight average molecular weight Mw of which is 5 million or more as measured by FFF-MALS and the average radius of gyration Rz of the polymer in the weight average molecular weight range of 5 million to 50 million is 130 nm or more, The rubber composition has a silica content of 20 parts by mass or more and 150 parts by mass or less based on 100 parts by mass of a rubber component.

9. the rubber composition includes natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a linear regression line having a slope of 0.25 or more in a region of a weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer; and silica; The rubber composition has a silica content of 20 parts by mass or more and 150 parts by mass or less based on 100 parts by mass of a rubber component.

10. A tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and a polymer radius of gyration Rz of 130 nm or more, carbon black and / or silica, and a solid resin.

11. A tire having a sidewall made using a rubber composition containing natural rubber derived from Russian dandelion, carbon black and / or silica, and a solid resin, the natural rubber having a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS and an average value of the radius of gyration Rz of a polymer in a weight average molecular weight range of 5 million to 50 million of 130 nm or more.

12. A tire having a sidewall made using a rubber composition containing: natural rubber derived from Russian dandelion, which has a weight average molecular weight Mw of 5 million or more as measured by FFF-MALS, and in which the slope of a linear regression line in a region of weight average molecular weight Mw of 5 million to 50 million in a plot of the common logarithm (logMw) of the weight average molecular weight Mw versus the common logarithm (logRz) of the radius of gyration Rz of the polymer is 0.25 or more; carbon black and / or silica; and a solid resin.

Citation Information

Patent Citations

  • Rubber composition for breaker and pneumatic tire

    JP2002338734A

  • Run-flat tire

    JP2009234374A

  • Method for analyzing rubber

    JP2012122796A

  • Natural rubber, and rubber composition and tire containing the same

    JP2013221069A

  • Manufacturing method of synthetic polyisoprene and synthetic polyisoprene

    JP2015205960A